5G SYSTEMS CONTAINING POLYMER COMPOSITIONS

By using polymer compositions of Naphtene-based hydroxycarbonate and liquid crystal polymer, the power consumption and heat increase of electrical components during high-frequency communication in 5G systems is solved, and the improvement of low dielectric constant and dielectric loss is achieved, and the high-frequency performance and mechanical characteristics of antenna elements and RF filters are improved.

JP7623358B2Active Publication Date: 2025-01-28TICONA LLC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022513101
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-27
Filing Date
2020-08-19
Publication Date
2025-01-28
Estimated Expiration
2040-08-19

AI Technical Summary

Technical Problem

In existing 5G systems, power consumption and heat increase in electrical components during high-frequency communication, and commonly used materials affect high-frequency performance, and improved electronic components are needed to solve this problem.

Method used

The polymer composition containing at least 10 mol.% Naphtene-based hydroxycarbonate and liquid crystal polymer is used for antenna elements and RF filters for 5G systems, with low dielectric constant and dielectric loss, combined with excellent thermomechanical properties and processability.

Benefits of technology

It achieves low dielectric constant and dielectric loss at 5G frequency, improves high frequency performance, and has good thermal mechanical characteristics and processability, and is suitable for antenna components and RF filters in 5G systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623358000024
    Figure 0007623358000024
  • Figure 0007623358000025
    Figure 0007623358000025
  • Figure 0007623358000026
    Figure 0007623358000026
Patent Text Reader

Abstract

A 5G system is provided that includes at least one antenna element configured to transmit and receive 5G radio frequency signals, and at least one electronic component. The antenna element, the electronic component, or both include a polymer composition that includes a liquid crystal polymer containing repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids in an amount of about 10 mol.% or greater. Furthermore, the polymer composition exhibits a dielectric constant of about 5 or less and a dielectric loss tangent of about 0.05 or less at a frequency of 10 GHz.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Cross-reference of related questions

[0001] This application is incorporated by reference in its entirety herein, inclusive of U.S. Provisional Patent Application No. 62 / 898,188, having a filing date of September 10, 2019; U.S. Provisional Patent Application No. 62 / 904,089, having a filing date of September 23, 2019; U.S. Provisional Patent Application No. 62 / 925,274, having a filing date of October 24, 2019; U.S. Provisional Patent Application No. 62 / 951,039, having a filing date of December 20, 2019; U.S. Provisional Patent Application No. 62 / 952,039, having a filing date of February 10, 2020; This application claims the benefit of U.S. Provisional Patent Application No. 62 / 972,195; U.S. Provisional Patent Application No. 62 / 986,072, having a filing date of March 6, 2020; U.S. Provisional Patent Application No. 62 / 994,321, having a filing date of March 25, 2020; U.S. Provisional Patent Application No. 63 / 008,989, having a filing date of April 13, 2020; U.S. Provisional Patent Application No. 63 / 024,560, having a filing date of May 14, 2020; and U.S. Provisional Patent Application No. 63 / 056,858, having a filing date of July 27, 2020. [Background technology]

[0002]

[0002] Various types of electrical components, such as antenna elements, radio frequency filters, and printed circuit boards, are utilized in 5G systems. Unfortunately, the high frequency transmission and reception encountered in 5G applications generally increases power consumption and heat generation. As a result, materials frequently used in conventional electronic components can adversely affect high frequency performance. Thus, there is a need for improved electronic components for use in 5G antenna systems. Summary of the Invention [Means for solving the problem]

[0003] According to one embodiment of the present invention, a 5G system is disclosed that includes at least one antenna element configured to transmit and receive 5G radio frequency signals and is provided with at least one electronic component. The antenna element, the electronic component, or both, include a polymer composition that includes a liquid crystal polymer containing repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids in an amount of about 10 mol.% or more. Furthermore, the polymer composition exhibits a relative dielectric constant of about 5 or less and a dissipation factor of about 0.05 or less at a frequency of 10 GHz.

[0004]

[0004] Other features and aspects of the present invention are described in more detail below.

[0005] A full and enabling disclosure of the present invention, including the best mode thereof, to one of ordinary skill in the art, is set forth more particularly in the remainder of the specification, including reference to the accompanying drawings, in which: [Brief description of the drawings]

[0005] [Figure 1]

[0006] FIG. 1 is a diagram of an embodiment of a 5G antenna system. [Figure 2A]

[0007] FIG. 1 illustrates a top view of an exemplary user computing device including a 5G antenna. [Figure 2B]

[0008] FIG. 2B is a side view of the example user computing device of FIG. 2A. [Diagram 3]

[0009] FIG. 2B is an expanded view of a portion of the user computing device of FIG. 2A. [Figure 4]

[0010] FIG. 1 is a side view of a coplanar waveguide antenna array configuration that can be used in a 5G antenna system. [Figure 5A]

[0011] FIG. 1 is a diagram of an antenna array for a large-scale multiple-input multiple-output configuration of a 5G antenna system. [Figure 5B]

[0012] FIG. 1 is a diagram of a formed antenna array that may be used in a 5G antenna system. [Figure 5C]

[0013] FIG. 1 is a diagram of an exemplary antenna configuration that may be used in a 5G antenna system. [Figure 6]

[0014] FIG. 1 is a schematic diagram of one embodiment of an RF SAW filter that can be used in the present invention. [Figure 7]

[0015] FIG. 1 is a schematic diagram of one embodiment of an RF BAW filter that can be used in the present invention. [Figure 8]

[0016] FIG. 2 is a schematic diagram of another embodiment of an RF SAW filter usable in the present invention. [Figure 9]

[0017] FIG. 1 is a schematic diagram of one embodiment of an RF cavity filter that can be used in the present invention. [Figure 10]

[0018] FIG. 1 is a schematic diagram of one embodiment of a circuit board usable in the present invention. [Figure 11]

[0019] FIG. 2 is a schematic diagram of another embodiment of a circuit board usable in the present invention. [Figure 12]

[0020] FIG. 2 is a schematic diagram of yet another embodiment of a circuit board usable in the present invention. [Figure 13]

[0021] FIG. 1 is a schematic diagram of one embodiment of a 5G system in which the circuit board can be utilized. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006]

[0022] It will be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention.

[0023] Generally, the present invention relates to 5G antenna systems that include electrical components (e.g., antenna structures, RF filters, circuit boards, etc.) that contain a polymer composition. The polymer composition typically contains a liquid crystal polymer having a "high naphthene" content insofar as it contains a relatively high content of repeat units derived from naphthenic hydroxycarboxylic acids and naphthenic dicarboxylic acids, such as NDA, HNA, or combinations thereof. That is, the total amount of repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids (e.g., NDA, HNA, or a combination of HNA and NDA) is typically about 10 mol.% or more of the polymer, in some embodiments about 12 mol.% or more, in some embodiments about 15 mol.% or more, in some embodiments about 18 mol.% or more, in some embodiments about 30 mol.% or more, in some embodiments about 40 mol.% or more, in some embodiments about 45 mol.% or more, in some embodiments about 50 mol.% or more, in some embodiments about 60 mol.% or more, in some embodiments about 62 mol.% or more, in some embodiments about 68 mol.% or more, in some embodiments about 70 mol.% or more, in some embodiments about 70 mol.% to about 80 mol.%. Without being limited by theory, it is believed that such "high naphthene" polymers can reduce the tendency of the polymer composition to absorb water, which can facilitate stabilization of the dielectric constant and dissipation factor in the high frequency range. That is, such high naphthenic polymers typically have a water absorption of about 0.015% or less, in some embodiments about 0.01% or less, and in some embodiments about 0.0001% to about 0.008% after immersion in water for 24 hours according to ISO 62-1: 2008. The high naphthenic polymers may also have a moisture absorption of about 0.01% or less, in some embodiments about 0.008% or less, and in some embodiments about 0.0001% to about 0.006% after exposure to a humid atmosphere (relative humidity 50%) at a temperature of 23° C. according to ISO 62-4: 2008.

[0007]

[0024] Thus, by carefully selecting the specific properties and concentrations of the components of the polymer composition, the inventors have discovered that the resulting composition can exhibit low dielectric constants and dielectric loss tangents over a wide range of frequencies, making it particularly suitable for use in 5G applications. That is, the polymer composition may exhibit a low dielectric constant of about 5 or less, in some embodiments about 4.5 or less, in some embodiments about 0.1 to about 4.4, in some embodiments about 1 to about 4.2, in some embodiments about 1.5 to about 4, in some embodiments about 2 to about 3.9, and in some embodiments about 3.5 to about 3.9 at typical 5G frequencies (e.g., 2 or 10 GHz). The dielectric loss tangent of the polymer composition, which is a measure of the rate of energy loss, may similarly be about 0.05 or less, in some embodiments about 0.01 or less, in some embodiments about 0.0001 to about 0.008, and in some embodiments about 0.0002 to about 0.006 at typical 5G frequencies (e.g., 2 or 10 GHz). Indeed, in some cases the dissipation factor may be very low, such as about 0.003 or less, in some embodiments about 0.002 or less, in some embodiments about 0.001 or less, in some embodiments about 0.0009 or less, in some embodiments about 0.0008 or less, and in some embodiments about 0.0001 to about 0.0007 at typical 5G frequencies (e.g., 2 or 10 GHz).

[0008]

[0025] Traditionally, it was believed that polymer compositions exhibiting low dielectric tangent and dielectric constant did not simultaneously have sufficiently good thermal, mechanical properties and ease of processing (i.e., low viscosity) to enable their use in certain types of applications. However, in contrast to conventional thinking, it has been found that polymer compositions have both excellent thermal, mechanical properties and processability. For example, the melting temperature of the polymer composition may be, for example, from about 200°C to about 400°C, in some embodiments from about 250°C to about 380°C, in some embodiments from about 270°C to about 360°C, and in some embodiments from about 300°C to about 350°C. Even at such melting temperatures, the ratio of the temperature deflection under load ("DTUL"), a measure of short-term heat resistance, to the melting temperature may still remain relatively high. For example, the ratio may range from about 0.5 to about 1.00, in some embodiments from about 0.6 to about 0.95, and in some embodiments from about 0.65 to about 0.85. Particular DTUL values ​​may be, for example, greater than about 160° C., in some embodiments, from about 170° C. to about 350° C., in some embodiments, from about 175° C. to about 320° C., and in some embodiments, from about 180° C. to about 290° C. Such high DTUL values ​​may, among other things, enable the use of fast and reliable surface mounting processes for mating the structure and other components of the electrical component.

[0009]

[0026] The polymer composition may also have excellent mechanical properties. For example, the polymer composition may exhibit a tensile strength of about 10 MPa or more, in some embodiments about 50 MPa or more, in some embodiments about 70 MPa to about 300 MPa, and in some embodiments about 80 MPa to about 200 MPa. The polymer composition may exhibit a tensile elongation of about 0.3% or more, in some embodiments about 0.4% or more, in some embodiments about 0.5% to about 4%, and in some embodiments about 0.5% to about 2%. The polymer composition may exhibit a tensile modulus of about 5,000 MPa or more, in some embodiments about 6,000 MPa or more, in some embodiments about 7,000 MPa to about 25,000 MPa, and in some embodiments about 10,000 MPa to about 20,000 MPa. Tensile properties may be determined according to ISO Test No. 527:2012 at a temperature of 23°C. Further, the polymer composition may exhibit a flexural strength of about 20 MPa or more, in some embodiments about 30 MPa or more, in some embodiments about 50 MPa or more, in some embodiments about 70 MPa to about 300 MPa, and in some embodiments about 80 MPa to about 200 MPa. The polymer composition may exhibit a flexural elongation of about 0.4% or more, in some embodiments about 0.5% to about 4%, and in some embodiments about 0.5% to about 2%. The polymer composition may exhibit a flexural modulus of about 5,000 MPa or more, in some embodiments about 6,000 MPa or more, in some embodiments about 7,000 MPa to about 25,000 MPa, and in some embodiments about 10,000 MPa to about 20,000 MPa. The flexural properties may be determined according to 178:2010 at a temperature of 23° C. Furthermore, the polymer composition may also have a high impact strength, which may be useful in forming thin substrates. For example, the polymer composition may exhibit a flexural elongation of about 3 kJ / m 2 or more, in some embodiments, about 5 kJ / m 2 or more, in some embodiments, about 7 kJ / m 2 or more, in some embodiments, about 8 kJ / m 2 ~about 40kJ / m 2 , in some embodiments, about 10 kJ / m 2 ~about 25kJ / m 2The impact strength may be determined in accordance with ISO Test No. ISO 179-1:2010 at a temperature of 23°C.

[0010]

[0027] Various embodiments of the invention will now be described in more detail. I. Polymer Composition A. Liquid Crystal Polymer

[0028] The polymer composition contains one or more liquid crystal polymers. Liquid crystal polymers generally have a rod-like structure and are classified as "thermotropic" as long as they are capable of exhibiting crystalline behavior in their molten state (e.g., thermotropic nematic state). Liquid crystal polymers utilized in the polymer composition typically have a melting temperature of about 200°C to about 400°C, in some embodiments about 250°C to about 380°C, in some embodiments about 270°C to about 360°C, and in some embodiments about 300°C to about 350°C. The melting temperature may be determined as known in the art using differential scanning calorimetry ("DSC"), for example, by ISO Test No. 11357-3:2011. Such polymers may be formed from one or more types of repeating units as known in the art. Liquid crystal polymers, for example, generally have the following formula (I):

[0011] [ka]

[0012] (In the formula, Ring B is a substituted or unsubstituted 6-membered aryl group (e.g., 1,4-phenylene or 1,3-phenylene), a substituted or unsubstituted 6-membered aryl group fused to a substituted or unsubstituted 5- or 6-membered aryl group (e.g., 2,6-naphthalene), or a substituted or unsubstituted 6-membered aryl group linked to a substituted or unsubstituted 5- or 6-membered aryl group (e.g., 4,4-biphenylene); Y1 and Y2 are independently O, C(O), NH, C(O)HN, or NHC(O). The aromatic ester may contain one or more aromatic ester repeat units represented by:

[0013]

[0029] Typically, at least one of Y1 and Y2 is C(O). Examples of such aromatic ester repeat units include, for example, aromatic dicarboxylic acid repeat units (in formula I, Y1 and Y2 are C(O)), aromatic hydroxycarboxylic acid repeat units (in formula I, Y1 is O and Y2 is C(O)), and various combinations thereof.

[0014]

[0030] For example, aromatic hydroxycarboxylic acid repeat units derived from aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid, 4-hydroxy-4'-biphenylcarboxylic acid, 2-hydroxy-6-naphthoic acid, 2-hydroxy-5-naphthoic acid, 3-hydroxy-2-naphthoic acid, 2-hydroxy-3-naphthoic acid, 4'-hydroxyphenyl-4-benzoic acid, 3'-hydroxyphenyl-4-benzoic acid, 4'-hydroxyphenyl-3-benzoic acid, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may be utilized. Particularly suitable aromatic hydroxycarboxylic acids are 4-hydroxybenzoic acid ("HBA") and 6-hydroxy-2-naphthoic acid (HNA). When utilized, repeat units derived from hydroxycarboxylic acids (e.g., HBA and / or HNA) typically comprise about 20 mol.% or more of the polymer, in some embodiments about 25 mol.% or more, in some embodiments about 30 mol.% or more, in some embodiments about 40 mol.% or more, in some embodiments about 50 mol.% or more, in some embodiments about 55 mol.% to 100 mol.%, and in some embodiments about 60 mol.% to about 95 mol.%.

[0015]

[0031] Also, aromatic dicarboxylic acid repeat units derived from aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, diphenylether-4,4'-dicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, bis(4-carboxyphenyl)ether, bis(4-carboxyphenyl)butane, bis(4-carboxyphenyl)ethane, bis(3-carboxyphenyl)ether, bis(3-carboxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may be utilized. Particularly suitable aromatic dicarboxylic acids can include, for example, terephthalic acid ("TA"), isophthalic acid ("IA"), and 2,6-naphthalenedicarboxylic acid ("NDA"). When utilized, repeat units derived from aromatic dicarboxylic acids (e.g., IA, TA, and / or NDA) each typically comprise from about 1 mol.% to about 40 mol.%, in some embodiments from about 2 mol.% to about 30 mol.%, and in some embodiments, from about 5 mol.% to about 25 mol.% of the polymer.

[0016]

[0032] Other repeat units can also be utilized in the polymer. For example, in certain embodiments, repeat units derived from aromatic diols such as hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl (or 4,4'-biphenol), 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, bis(4-hydroxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, may be utilized. Particularly suitable aromatic diols can include, for example, hydroquinone ("HQ") and 4,4'-biphenol ("BP"). When utilized, repeat units derived from aromatic diols (e.g., HQ and / or BP) typically comprise from about 1 mol.% to about 50 mol.%, in some embodiments from about 1 mol.% to about 40 mol.%, in some embodiments from about 2 mol.% to about 40 mol.%, in some embodiments from about 5 mol.% to about 35 mol.%, and in some embodiments from about 5 mol.% to about 25 mol.% of the polymer.

[0017]

[0033] Repeat units such as those derived from aromatic amides (e.g., acetaminophen ("APAP")), and / or aromatic amines (e.g., 4-aminophenol ("AP"), 3-aminophenol, 1,4-phenylenediamine, 1,3-phenylenediamine, etc.) may also be utilized. When utilized, repeat units derived from aromatic amides (e.g., APAP) and / or aromatic amines (e.g., AP) typically comprise from about 0.1 mol.% to about 20 mol.%, in some embodiments from about 0.5 mol.% to about 15 mol.%, and in some embodiments from about 1 mol.% to about 10% of the polymer. It should also be understood that various other monomeric repeat units may be incorporated into the polymer. For example, in certain embodiments, the polymer may contain one or more repeat units derived from non-aromatic monomers, such as aliphatic or alicyclic hydroxycarboxylic acids, dicarboxylic acids, diols, amides, amines, and the like. Of course, in other embodiments, the polymer may be "fully aromatic" in that it does not include repeat units derived from non-aromatic (e.g., aliphatic or alicyclic) monomers.

[0018]

[0034] As mentioned above, the liquid crystal polymer is a "high naphthene" polymer insofar as it contains a relatively high content of repeat units derived from naphthenic hydroxycarboxylic acids and naphthenic dicarboxylic acids, typically NDA, HNA, or a combination thereof. That is, the total amount of repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids (e.g., NDA, HNA, or a combination of HNA and NDA) is typically about 10 mol.% or more of the polymer, in some embodiments about 12 mol.% or more, in some embodiments about 15 mol.% or more, in some embodiments about 18 mol.% or more, in some embodiments about 30 mol.% or more, in some embodiments about 40 mol.% or more, in some embodiments about 45 mol.% or more, in some embodiments about 50 mol.% or more, in some embodiments about 60 mol.% or more, in some embodiments about 62 mol.% or more, in some embodiments about 68 mol.% or more, in some embodiments about 70 mol.% or more, in some embodiments about 70 mol.% to about 80 mol.%.

[0019]

[0035] In one embodiment, for example, the repeat unit derived from HNA may constitute 30 mol.% or more of the polymer, in some embodiments, about 40 mol.% or more, in some embodiments, about 45 mol.% or more, in some embodiments, 50 mol.% or more, in some embodiments, about 60 mol.% or more, in some embodiments, about 62 mol.% or more, in some embodiments, about 68 mol.% or more, in some embodiments, about 70 mol.% or more, in some embodiments, about 70 mol.% to about 80 mol.%. The liquid crystal polymer may also contain various other monomers. For example, the polymer may contain about 10 mol.% to about 40 mol.%, in some embodiments, about 15 mol.% to about 35 mol.%, and in some embodiments, about 20 mol.% to about 30 mol.% of the repeat unit derived from HBA. When utilized, the molar ratio of HNA to HBA may be selectively controlled within a particular range to facilitate achievement of desired properties, for example, from about 0.1 to about 40, in some embodiments from about 0.5 to about 20, in some embodiments from about 0.8 to about 10, and in some embodiments from about 1 to about 5. The polymer may also contain aromatic dicarboxylic acids (e.g., IA and / or TA) in an amount of from about 1 mol.% to about 40 mol.%, in some embodiments from about 5 mol.% to about 25 mol.%, and / or aromatic diols (e.g., BP and / or HQ) in an amount of from about 1 mol.% to about 40 mol.%, in some embodiments from about 5 mol.% to about 25 mol.%. However, in some cases, it may be desirable to minimize the presence of such monomers in the polymer to facilitate achievement of desired properties. For example, the total amount of aromatic dicarboxylic acids (e.g., IA and / or TA) may be about 20 mol.% or less, in some embodiments about 15 mol.% or less, in some embodiments about 10 mol.% or less, in some embodiments, 0 mol.% to about 5 mol.%, and in some embodiments, 0 mol.% to about 2 mol.% of the polymer.Similarly, the total amount of aromatic dicarboxylic acids (e.g., IA and / or TA) may be about 20 mol.% or less of the polymer, in some embodiments about 15 mol.% or less, in some embodiments about 10 mol.% or less, in some embodiments, 0 mol.% to about 5 mol.%, and in some embodiments, 0 mol.% to about 2 mol.% (e.g., 0 mol.%).

[0020]

[0036] In another embodiment, the repeat unit derived from NDA may constitute 10 mol.% or more of the polymer, in some embodiments, about 12 mol.% or more, in some embodiments, about 15 mol.% or more, and in some embodiments, about 18 mol.% to about 95 mol.%. In such an embodiment, the liquid crystal polymer may further contain various other monomers, such as aromatic hydroxycarboxylic acid (e.g., HBA) in an amount of about 20 mol.% to about 60 mol.%, in some embodiments, about 30 mol.% to about 50 mol.%, aromatic dicarboxylic acid (e.g., IA and / or TA) in an amount of about 2 mol.% to about 30 mol.%, in some embodiments, about 5 mol.% to about 25 mol.%, and / or aromatic diol (e.g., BP and / or HQ) in an amount of about 2 mol.% to about 40 mol.%, in some embodiments, about 5 mol.% to about 35 mol.%.

[0021]

[0037] Regardless of the specific components and properties of the polymer, the liquid crystal polymer may be prepared by first introducing aromatic monomers used to form ester repeat units (e.g., aromatic hydroxycarboxylic acids, aromatic dicarboxylic acids, etc.) and / or other repeat units (e.g., aromatic diols, aromatic amides, aromatic amines, etc.) into a reaction vessel and initiating a polycondensation reaction. The specific conditions and steps utilized in such reactions are well known and may be described in more detail in U.S. Pat. No. 4,161,470 to Calundann; U.S. Pat. No. 5,616,680 to Linstid, III, et al.; U.S. Pat. No. 6,114,492 to Linstid, III, et al.; U.S. Pat. No. 6,514,611 to Shepherd, et al.; and WO 2004 / 058851 to Waggoner. The vessel utilized for the reaction is not particularly limited, but it is typically desirable to utilize one commonly used in the reaction of high viscosity fluids. Examples of such reaction vessels include stirred tank type devices having agitators with various shapes of stirring blades, such as anchor type, multi-stage type, helical ribbon type, screw shaft type, etc., or modified forms thereof. Further examples of such reaction vessels include mixing devices commonly used in resin kneading, such as kneaders, roll mills, Banbury mixers, etc.

[0022]

[0038] If desired, the reaction may proceed by acetylation of the monomer as known in the art. This may be accomplished by adding an acetylating agent (e.g., acetic anhydride) to the monomer. Acetylation is generally initiated at a temperature of about 90° C. In the early stages of acetylation, reflux may be utilized to maintain the vapor phase temperature below the point where the acetic acid by-product and anhydride begin to distill. The temperature during acetylation typically ranges between 90° C. and 150° C., and in some embodiments, from about 110° C. to about 150° C. If reflux is used, the vapor phase temperature typically exceeds the boiling point of acetic acid, but remains low enough to retain residual acetic anhydride. For example, acetic anhydride vaporizes at a temperature of about 140° C. Thus, it is particularly desirable to provide a vapor phase reflux at a temperature of about 110° C. to about 130° C. in the reactor. An excess of acetic anhydride may be utilized to ensure a substantially complete reaction. The amount of excess anhydride will vary depending on the particular acetylation conditions utilized, including the presence or absence of reflux. It is not uncommon to use an excess of acetic anhydride of from about 1 to about 10 mole percent based on the total moles of reactant hydroxyl groups present.

[0023]

[0039] Acetylation may be carried out in a separate reaction vessel or in situ in the polymerization reaction vessel. If a separate reaction vessel is utilized, one or more of the monomers may be introduced into the acetylation reactor and then transferred to the polymerization reactor. Similarly, one or more of the monomers may be introduced directly into the reaction vessel without prior acetylation.

[0024]

[0040] In addition to the monomer and optional acetylating agent, other components may be included in the reaction mixture to facilitate polymerization. For example, catalysts such as metal salt catalysts (e.g., magnesium acetate, tin(I) acetate, tetrabutyl titanate, lead acetate, sodium acetate, potassium acetate, etc.) and organic compound catalysts (e.g., N-methylimidazole) may be optionally utilized. Such catalysts are typically used in amounts of about 50 to about 500 parts per million based on the total weight of the repeat unit precursor. When separate reactors are utilized, it is typically desirable to apply the catalyst to the acetylation reactor rather than the polymerization reactor, although this is by no means required.

[0025]

[0041] To initiate melt polycondensation of the reactants, the reaction mixture is typically heated to an elevated temperature in a polymerization reactor. For example, polycondensation may be carried out within a temperature range of about 250°C to about 380°C, and in some embodiments, about 280°C to about 380°C. For example, one suitable technique for forming aromatic polyesters involves charging the precursor monomers and acetic anhydride to a reactor, heating the mixture to a temperature of about 90°C to about 150°C, acetylating the hydroxyl groups of the monomers (e.g., forming acetoxy), and then increasing the temperature to about 280°C to about 380°C to carry out melt polycondensation. As the final polymerization temperature is approached, volatile by-products of the reaction (e.g., acetic acid) can also be removed so that the desired molecular weight is readily achievable. The reaction mixture is typically agitated during polymerization to ensure good heat and mass transfer, and therefore good material homogeneity. The rotation speed of the agitator may vary during the reaction, but typically ranges from about 10 to about 100 revolutions per minute ("rpm"), and in some embodiments, from about 20 to about 80 rpm. To enhance the molecular weight in the melt, the polymerization reaction may also be carried out under vacuum, the application of which aids in the removal of volatiles formed during the final stages of polycondensation. The vacuum may be created by applying a suction pressure, for example, in the range of about 5 to about 30 pounds per square inch ("psi"), and in some embodiments, about 10 to about 20 psi.

[0026]

[0042] After melt polymerization, the molten polymer can be discharged from the reactor through an extrusion orifice, typically with a die of the desired shape, cooled, and collected. Generally, the melt is discharged through a perforated die to form strands that are drawn into a water bath, pelletized, and dried. In some embodiments, the melt-polymerized polymer can be subsequently subjected to a solid-state polymerization process to further increase its molecular weight. The solid-state polymerization can be carried out in the presence of a gas (e.g., air, an inert gas, etc.). Suitable inert gases can include, for example, nitrogen, helium, argon, neon, krypton, xenon, etc., and combinations thereof. The solid-state polymerization reaction vessel can be of virtually any design capable of maintaining the polymer at the desired solid-state polymerization temperature for the desired residence time. Examples of such vessels can have fixed beds, stationary beds, moving beds, fluidized beds, etc. The temperature at which the solid-state polymerization is carried out can vary, but is typically in the range of about 250°C to about 350°C. Of course, the polymerization time will vary based on the temperature and the target molecular weight. In most cases, however, the solid state polymerization time is from about 2 to about 12 hours, and in some embodiments, from about 4 to about 10 hours.

[0027]

[0043] Generally, the total amount of crystalline polymer utilized in the polymer composition is about 40 wt.% to about 99.5 wt.%, in some embodiments about 50 wt.% to about 99 wt.%, in some embodiments about 60 wt.% to about 98 wt.%, and in some embodiments about 70 wt.% to about 95 wt.% of the polymer composition. In certain embodiments, all of the liquid crystal polymers are "high naphthene" polymers such as those described above. However, in other embodiments, "low naphthene" liquid crystal polymers may be utilized in the composition, in which the total amount of repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids (e.g., NDA, HNA, or a combination of HNA and NDA) is less than 10 mol.%, in some embodiments about 8 mol.% or less, in some embodiments about 6 mol.% or less, and in some embodiments about 1 mol.% to about 5 mol.% of the polymer. If utilized, it is generally desirable that such low naphthene polymers are present only in relatively low amounts. For example, when utilized, the low naphthene liquid crystalline polymer typically comprises from about 1 wt.% to about 50 wt.%, in some embodiments from about 2 wt.% to about 40 wt.%, in some embodiments from about 5 wt.% to about 30 wt.%, of the total amount of liquid crystalline polymer in the composition, and from about 0.5 wt.% to about 45 wt.%, in some embodiments from about 2 wt.% to about 35 wt.%, and in some embodiments from about 5 wt.% to about 25 wt.% of the total composition. In contrast, the high naphthene liquid crystalline polymer typically comprises from about 50 wt.% to about 99 wt.%, in some embodiments from about 60 wt.% to about 98 wt.%, and in some embodiments from about 70 wt.% to about 95 wt.%, of the total amount of liquid crystalline polymer in the composition, and from about 55 wt.% to about 99.5 wt.%, in some embodiments from about 65 wt.% to about 98 wt.%, and in some embodiments from about 75 wt.% to about 95 wt.% of the total composition.

[0028] B. Optional Additives

[0044] The liquid crystal polymer may be utilized in the polymer composition in neat form (i.e., 100 wt.% of the polymer composition), or a wide variety of other additives may be optionally included in the composition. If utilized, such additives typically comprise from about 1 wt.% to about 60 wt.%, in some embodiments from about 2 wt.% to about 50 wt.%, and in some embodiments, from about 5 wt.% to about 40 wt.% of the polymer composition. In such embodiments, the liquid crystal polymer may similarly comprise from about 40 wt.% to about 99 wt.%, in some embodiments from about 50 wt.% to about 98 wt.%, and in some embodiments, from about 60 wt.% to about 95 wt.% of the polymer composition.

[0029]

[0045] A wide variety of additional additives may also be included in the polymer composition, such as hydrophobic materials, lubricants, fibrous fillers, particulate fillers, hollow fillers, laser activatable additives, thermally conductive fillers, pigments, antioxidants, stabilizers, surfactants, waxes, flame retardants, anti-sag additives, nucleating agents (e.g., boron nitride), flow modifiers, coupling agents, antimicrobial agents, pigments or other colorants, impact modifiers, and other materials added to improve properties and processability.

[0030] i. Hydrophobic Materials

[0046] If desired, a hydrophobic material can also be utilized in the polymer composition, which can help further reduce the tendency of the polymer composition to absorb water, thereby assisting in stabilizing the dielectric constant and dissipation factor in the high frequency range. If utilized, the weight ratio of the liquid crystal polymer to the hydrophobic material is typically from about 1 to about 20, in some embodiments from about 2 to about 15, and in some embodiments from about 3 to about 10. For example, the hydrophobic material may comprise from about 1 wt.% to about 60 wt.%, in some embodiments from about 2 wt.% to about 50 wt.%, and in some embodiments from about 5 wt.% to about 40 wt.% of the total polymer composition.

[0031]

[0047] Particularly suitable hydrophobic materials are low surface energy elastomers such as fluoropolymers, silicone polymers, etc. Fluoropolymers may contain, for example, a hydrocarbon backbone polymer in which some or all of the hydrogen atoms are replaced with fluorine atoms. The backbone polymer may be polyolefin-based and formed from unsaturated olefin monomers substituted with fluorine. The fluoropolymer may be a homopolymer of such fluorine-substituted monomers or a copolymer of fluorine-substituted monomers, or a mixture of fluorine-substituted and non-fluorine-substituted monomers. Along with fluorine atoms, the fluoropolymer may be substituted with other halogen atoms such as chlorine and bromine atoms. Representative monomers suitable for forming the fluoropolymers used in the present invention are tetrafluoroethylene ("TFE"), vinylidene fluoride ("VF2"), hexafluoropropylene ("HFP"), chlorotrifluoroethylene ("CTFE"), perfluoroethyl vinyl ether ("PEVE"), perfluoromethyl vinyl ether ("PMVE"), perfluoropropyl vinyl ether ("PPVE"), etc., and mixtures thereof. Specific examples of suitable fluoropolymers include polytetrafluoroethylene ("PTFE"), perfluoroalkyl vinyl ether ("PVE"), poly(tetrafluoroethylene-co-perfluoroalkyl vinyl ether) ("PFA"), fluorinated ethylene propylene copolymer ("FEP"), ethylene tetrafluoroethylene copolymer ("ETFE"), polyvinylidene fluoride ("PVDF"), polychlorotrifluoroethylene ("PCTFE"), and TFE copolymers with VF2 and / or HFP, and mixtures thereof.

[0032]

[0048] In certain embodiments, the hydrophobic material (e.g., fluoropolymer) may have a particle size that is selectively controlled to promote the formation of a relatively low thickness film. For example, the hydrophobic material may have a median particle size (e.g., diameter) of about 1 to about 60 micrometers, in some embodiments about 2 to about 55 micrometers, in some embodiments about 3 to about 50 micrometers, and in some embodiments about 25 to about 50 micrometers, as determined using laser diffraction techniques (e.g., using a Horiba LA-960 particle size distribution analyzer), for example, according to ISO-13320:2009. The hydrophobic material may also have a narrow size distribution. That is, at least about 70% by volume of the particles, in some embodiments at least about 80% by volume of the particles, and in some embodiments at least about 90% by volume of the particles may have a size within the ranges mentioned above.

[0033] ii. Fibrous Fillers

[0049] For example, in one embodiment, fibrous fillers may be utilized in the polymer composition in an amount of about 1 wt.% to about 40 wt.%, in some embodiments about 3 wt.% to about 30 wt.%, in some embodiments about 5 wt.% to about 20 wt.%, etc. of the polymer composition. Fibrous fillers typically include fillers that have a high degree of tensile strength relative to their mass. For example, the ultimate tensile strength of the fibers (determined according to ASTM D2101) is typically about 1,000 to about 15,000 megapascals ("MPa"), in some embodiments about 2,000 MPa to about 10,000 MPa, and in some embodiments about 3,000 MPa to about 6,000 MPa. To help maintain desired dielectric properties, such high strength fibers may be formed from materials that are generally insulating in nature, such as glass, ceramic or mineral (e.g., alumina or silica), aramid (e.g., Kevlar® sold by EI duPont de Nemours, Wilmington, Del.), mineral, polyolefin, polyester, and the like. The fibrous filler may include glass fiber, mineral fiber, or mixtures thereof. For example, in one embodiment, the fibrous filler may include glass fiber. Particularly suitable glass fibers may include E-glass, A-glass, C-glass, D-glass, AR-glass, R-glass, S1-glass, S2-glass, and the like. In another embodiment, the fibrous filler may include mineral fiber. Mineral fibers may include those derived from silicates, such as neosilicates, sorosilicates, inosilicates (e.g., calcium inosilicates such as wollastonite; calcium magnesium inosilicates such as tremolite; calcium magnesium iron inosilicates such as actinolite; magnesium iron inosilicates such as anthophillite, etc.), phyllosilicates (e.g., aluminum phyllosilicates such as palygorskite), tectosilicates, etc.; sulfates such as calcium sulfate (e.g., dehydrated or anhydrous gypsum); mineral wool (e.g., rock or slag wool), etc. Particularly suitable are inosilicates, such as wollastonite fibers available from Nyco Minerals under the trade name NYGLOS® (e.g., NYGLOS® 4W or NYGLOS® 8).

[0034]

[0050] Furthermore, although the fibrous filler may have a variety of different sizes, fibers having a particular aspect ratio may promote improvement of the mechanical properties of the polymer composition. That is, fibrous fillers having an aspect ratio (average length divided by nominal diameter) of about 2 or more, in some embodiments about 4 or more, in some embodiments about 5 to about 50, and in some embodiments about 8 to about 40 may be particularly beneficial. Such fibrous fillers may have a weight average length of, for example, about 10 micrometers or more, in some embodiments about 25 micrometers or more, in some embodiments about 50 micrometers or more to about 800 micrometers or less, and in some embodiments about 60 micrometers to about 500 micrometers. Also, such fibrous fillers may have a volume average length of, for example, about 10 micrometers or more, in some embodiments about 25 micrometers or more, in some embodiments about 50 micrometers or more to about 800 micrometers or less, and in some embodiments about 60 micrometers to about 500 micrometers. The fibrous filler may similarly have a nominal diameter of about 5 micrometers or more, in some embodiments about 6 micrometers or more, in some embodiments about 8 micrometers to about 40 micrometers, and in some embodiments about 9 micrometers to about 20 micrometers. The relative amount of fibrous filler may also be selectively controlled to facilitate achieving the desired mechanical and thermal properties without adversely affecting other properties of the polymer composition, such as its flowability and dielectric properties. In this regard, the fibrous filler may have a relative dielectric constant of about 6 or less, in some embodiments about 5.5 or less, in some embodiments about 1.1 to about 5, and in some embodiments about 2 to about 4.8 at a frequency of 1 GHz.

[0035]

[0051] The fibrous filler may be in modified or unmodified form and may be sized or chemically treated, for example to improve adhesion to plastics. In some cases, glass fibers may be sized to protect them and smooth them, as well as improve adhesion between the fibers and the matrix material. If present, the sizing may include silanes, film formers, lubricants, wetting agents, adhesives, optionally antistatic agents and plasticizers, emulsifiers, and optionally further additives. In one particular embodiment, the sizing may include silanes. Particular examples of silanes are aminosilanes, such as 3-trimethoxysilylpropylamine, N-(2-aminoethyl)-3-aminopropyltrimethoxy-silane, N-(3-trimethoxysilanylpropyl)ethane-1,2-diamine, 3-(2-aminoethyl-amino)propyltrimethoxysilane, N-[3-(trimethoxysilyl)propyl]-1,2-ethane-diamine.

[0036] iii. Laser Activatable Additives

[0052] In certain other embodiments, the polymer composition may be "laser activatable" in the sense that it contains an additive that can be activated by a laser direct structuring ("LDS") process. In such a process, the additive is exposed to a laser that causes the liberation of metal. The laser thereby patterns the conductive elements in the part, leaving a roughened surface containing embedded metal particles. These particles act as nuclei for crystal growth during a subsequent plating process (e.g., copper plating, gold plating, nickel plating, silver plating, zinc plating, tin plating, etc.). The laser activatable additive generally comprises a spinel crystal, which may contain two or more metal oxide cluster configurations within a definable crystal formation. For example, all crystal formations may be represented by the following general formula: AB2O4 (In the formula, A is a metal cation having a valence of two, such as cadmium, chromium, manganese, nickel, zinc, copper, cobalt, iron, magnesium, tin, titanium, and the like, and combinations thereof; B is a metal cation having a valence of 3, such as chromium, iron, aluminum, nickel, manganese, tin, and combinations thereof. may have the following structure:

[0037]

[0053] Typically, A in the above formula provides the main cation component of the first metal oxide cluster, and B provides the main cation component of the second metal oxide cluster. These oxide clusters may have the same or different structures. For example, in one embodiment, the first metal oxide cluster has a tetrahedral structure and the second metal oxide cluster has an octahedral cluster. Nevertheless, the clusters can be combined to provide a single identifiable crystal type structure with increased sensitivity to electromagnetic radiation. Examples of suitable spinel crystals include, for example, MgAl2O4, ZnAl2O4, FeAl2O4, CuFe2O4, CuCr2O4, MnFe2O4, NiFe2O4, TiFe2O4, FeCr2O4, MgCr2O4, and the like. Copper chromium oxide (CuCr2O4) is particularly suitable for use in the present invention and is available from Shepherd Color Co. under the name "Shepherd Black 1GM".

[0038]

[0054] The laser activatable additive may comprise from about 0.1 wt.% to about 30 wt.%, in some embodiments from about 0.5 wt.% to about 20 wt.%, and in some embodiments, from about 1 wt.% to about 10 wt.% of the polymer composition.

[0039] iv. Hollow Filler

[0055] Although by no means required, the polymer composition may also include one or more hollow inorganic fillers to aid in achieving a desired dielectric constant. For example, such fillers may have a dielectric constant at 100 MHz of about 3.0 or less, in some embodiments about 2.5 or less, in some embodiments about 1.1 to about 2.3, and in some embodiments about 1.2 to about 2.0. Hollow inorganic fillers typically have an internal hollow space or cavity and may be synthesized using techniques known in the art. Hollow inorganic fillers may be made from conventional materials. For example, hollow inorganic fillers may include alumina, silica, zirconia, magnesia, glass, fly ash, borates, phosphates, ceramics, and the like. In one embodiment, hollow inorganic fillers may include hollow glass fillers, hollow ceramic fillers, and mixtures thereof. In one embodiment, the hollow inorganic fillers include hollow glass fillers. The hollow glass filler may be made from soda lime borosilicate glass, soda lime glass, borosilicate glass, sodium borosilicate glass, sodium silicate glass, or aluminosilicate glass. In this regard, in one embodiment, the composition of the glass may be, but is not limited to, at least about 65% by weight SiO2, 3-15% by weight Na2O, 8-15% by weight CaO, 0.1-5% by weight MgO, 0.01-3% by weight Al2O3, 0.01-1% by weight K2O, and optionally other oxides (e.g., Li2O, Fe2O3, TiO2, B2O3). In another embodiment, the composition may be about 50-58% by weight SiO2, 25-30% by weight Al2O3, 6-10% by weight CaO, 1-4% by weight Na2O / K2O, and 1-5% by weight other oxides. Further, in one embodiment, the hollow glass filler may include more alkaline earth metal oxide than alkali metal oxide. For example, the weight ratio of alkaline earth metal oxide to alkali metal oxide may be greater than 1, in some embodiments greater than about 1.1, in some embodiments from about 1.2 to about 4, and in some embodiments from about 1.5 to about 3. Notwithstanding the above, it should be understood that the composition of the glass may vary depending on the type of glass utilized and still provide the benefits desired by the present invention.

[0040]

[0056] The hollow inorganic filler may have at least one dimension having an average value of about 1 micrometer or more, in some embodiments about 5 micrometers or more, in some embodiments about 8 micrometers or more, in some embodiments about 1 micrometer to about 150 micrometers, in some embodiments about 10 micrometers to about 150 micrometers, and in some embodiments about 12 micrometers to about 50 micrometers. In one embodiment, such average value is d 50 Further, the hollow inorganic filler may have a D value of about 3 micrometers or more, in some embodiments about 4 micrometers or more, in some embodiments from about 5 micrometers to about 20 micrometers, and in some embodiments from about 6 micrometers to about 15 micrometers. 10 The hollow inorganic filler may have a D of about 10 micrometers or more, in some embodiments about 15 micrometers or more, in some embodiments from about 20 micrometers to about 150 micrometers, and in some embodiments, from about 22 micrometers to about 50 micrometers. 90In this regard, the hollow inorganic filler may be present in a size distribution that may be Gaussian, normal or non-normal. In one embodiment, the hollow inorganic filler may have a Gaussian size distribution. In another embodiment, the hollow inorganic filler may have a normal size distribution. In a further embodiment, the hollow inorganic filler may have a non-normal size distribution. Examples of non-normal size distributions may include unimodal and multimodal (e.g., bimodal) size distributions. When referring to the above dimensions, such dimensions may be any dimension. However, in one embodiment, such dimensions refer to diameters. For example, such values ​​for dimensions refer to the average diameter of a sphere. Dimensions such as average diameters may be determined according to 3M QCM 193.0. In this regard, in one embodiment, the hollow inorganic filler may refer to hollow spheres, such as hollow glass spheres. For example, the hollow inorganic filler may have an average aspect ratio of approximately 1. Generally, the average aspect ratio may be greater than or equal to about 0.8, and in some embodiments greater than or equal to about 0.85, and in some embodiments, from about 0.9 to about 1.3, and in some embodiments, from about 0.95 to about 1.05.

[0041]

[0057] In addition, the hollow inorganic filler may have a relatively thin wall to aid in the dielectric properties and weight reduction of the polymer composition. The wall thickness may be about 50% or less, in some embodiments about 40% or less, in some embodiments about 1% to about 30%, and in some embodiments about 2% to about 25% of the average dimension, e.g., average diameter, of the hollow inorganic filler. In addition, the hollow inorganic filler may have a particular true density that allows for easy handling and can provide a polymer composition with reduced weight. Generally, true density refers to the quotient obtained by dividing the mass of a hollow filler sample by the true volume of the mass of the hollow filler, where the true volume is referred to as the total volume of the hollow filler. In this regard, the true density of the hollow inorganic filler is about 0.1 g / cm 3 or more, in some embodiments, about 0.2 g / cm 3 or more, in some embodiments, about 0.3 g / cm 3 More than ~ approx. 1.2g / cm 3 , in some embodiments, about 0.4 g / cm 3More than ~ approx. 0.9g / cm 3 True density may be determined according to 3M QCM 14.24.1.

[0042]

[0058] Even when the fillers are hollow, they may have mechanical strength that allows them to maintain their structural integrity and reduces the likelihood that the fillers will break during processing and / or use. In this regard, the isotactic crush resistance of hollow inorganic fillers (i.e., at least 80 vol.%, e.g., at least 90 vol.%, of the hollow filler survives) may be about 20 MPa or more, in some embodiments about 100 MPa or more, in some embodiments about 150 MPa to about 500 MPa, and in some embodiments about 200 MPa to about 350 MPa. The isotactic crush resistance may be determined according to 3M QCM 14.1.8.

[0043]

[0059] The alkalinity of the hollow inorganic filler may be about 1.0 meq / g or less, in some embodiments about 0.9 meq / g or less, in some embodiments about 0.1 meq / g to about 0.8 meq / g, in some embodiments about 0.2 meq / g to about 0.7 meq / g. The alkalinity may be determined according to 3M QCM 55.19. To provide a relatively low alkalinity, the hollow inorganic filler may be treated with a suitable acid, such as phosphoric acid. Additionally, the hollow inorganic filler may also include a surface treatment to help provide better compatibility with other components in the polymer and / or polymer composition. By way of example, the surface treatment may be silanization. In particular, the surface treatment may include, but is not limited to, aminosilanes, epoxysilanes, and the like.

[0044]

[0060] If utilized, hollow inorganic fillers may comprise, for example, about 1 wt.% or more, in some embodiments about 4 wt.% or more, in some embodiments, about 5 wt.% to about 40 wt.%, and in some embodiments, about 10 wt.% to about 30 wt.% of the polymer composition.

[0045] v. Particulate Fillers

[0061] If desired, particulate fillers may be utilized to improve certain properties of the polymer composition. The particulate fillers may be utilized in the polymer composition in an amount of about 5 to about 60 parts by weight, in some embodiments about 10 to about 50 parts by weight, and in some embodiments about 15 to about 40 parts by weight per 100 parts of liquid crystal polymer utilized in the polymer composition. For example, the particulate fillers may comprise about 5 wt.% to about 50 wt.%, in some embodiments about 10 wt.% to about 40 wt.%, and in some embodiments about 15 wt.% to about 30 wt.% of the polymer composition.

[0046]

[0062] In certain embodiments, particles having certain hardness values ​​may be utilized to aid in improving the surface properties of the composition. For example, the hardness value may be about 2 or more, in some embodiments about 2.5 or more, in some embodiments about 3 to about 11, in some embodiments about 3.5 to about 11, and in some embodiments about 4.5 to about 6.5 based on the Mohs hardness scale. Examples of such particles include silica (Mohs hardness 7), mica (Mohs hardness about 3); carbonates such as calcium carbonate (CaCO3, Mohs hardness 3.0), or copper hydroxide carbonate (Cu2CO3(OH)2, Mohs hardness 4.0); fluorides such as calcium fluoride (CaFl2, Mohs hardness 4.0); calcium pyrophosphate (Ca2P2O7, Mohs hardness 5.0), anhydrous dicalcium phosphate (CaHPO4, Mohs hardness 3.5). , or phosphates such as hydrated aluminum phosphate (AlPO4·2H2O; Mohs hardness 4.5); borates such as calcium borosilicate hydroxide (Ca2B5SiO9(OH)5, Mohs hardness 3.5); alumina (AlO2, Mohs hardness 10.0); sulfates such as calcium sulfate (CaSO4, Mohs hardness 3.5) or barium sulfate (BaSO4, Mohs hardness 3-3.5), and combinations thereof.

[0047]

[0063] The shape of the particles may vary as desired. For example, certain embodiments may utilize flake-shaped particles having a relatively high aspect ratio (e.g., average diameter divided by average thickness), such as about 10:1 or more, in some embodiments about 20:1 or more, and in some embodiments, about 40:1 to about 200:1. The average diameter of the particles may range from about 5 micrometers to about 200 micrometers, in some embodiments about 30 micrometers to about 150 micrometers, and in some embodiments about 50 micrometers to about 120 micrometers, as determined using laser diffraction techniques (e.g., using a Horiba LA-960 particle size distribution analyzer), for example, according to ISO 13320:2009. Suitable flake-shaped particles may be formed from natural and / or synthetic silicate minerals, such as mica, halloysite, kaolinite, illite, montmorillonite, vermiculite, palygorskite, pyrophyllite, calcium silicate, aluminum silicate, wollastonite, and the like. For example, mica is particularly suitable. For example, muscovite (KAl2(AlSi3)O 10 (OH)2), biotite (K(Mg,Fe)3(AlSi3)O 10 (OH)2), phlogopite (KMg3(AlSi3)O 10 (OH)2), red mica (K(Li,Al) 2-3 (AlSi3)O 10 (OH)2), glauconite (K,Na)(Al,Mg,Fe)2(Si,Al)4O 10 Mica in any form, including, for example, methyl methacrylate (OH)2), may generally be utilized. Granular particles may also be utilized. Typically, such particles have an average diameter of about 0.1 to about 10 micrometers, in some embodiments about 0.2 to about 4 micrometers, and in some embodiments about 0.5 to about 2 micrometers, as determined using laser diffraction techniques (e.g., using a Horiba LA-960 particle size distribution analyzer), for example, according to ISO 13320:2009. Particularly suitable granular fillers may include, for example, talc, barium sulfate, calcium sulfate, calcium carbonate, and the like.

[0048]

[0064] The particulate filler may be formed primarily or entirely of one type of particle, such as flake-shaped particles (e.g., mica) or granular particles (e.g., barium sulfate). That is, such flake-shaped or granular particles may comprise about 50 wt.% or more, and in some embodiments about 75 wt.% or more (e.g., 100 wt.%) of the particulate filler. Of course, in other embodiments, flake-shaped and granular particles may be utilized in combination. In such embodiments, for example, the flake-shaped particles may comprise about 0.5 wt.% to about 20 wt.%, and in some embodiments about 1 wt.% to about 10 wt.%, of the particulate filler, while the granular particles may comprise about 80 wt.% to about 99.5 wt.%, and in some embodiments about 90 wt.% to about 99 wt.% of the particulate filler.

[0049]

[0065] If desired, the particles may also be coated with a fluorinated additive to help improve the processing of the composition, for example by providing better mold filling, internal lubrication, mold release, etc. The fluorinated additive may include a fluoropolymer containing a hydrocarbon backbone polymer in which some or all of the hydrogen atoms are replaced with fluorine atoms. The backbone polymer may be polyolefin-based and formed from an unsaturated olefin monomer substituted with fluorine. The fluoropolymer may be a homopolymer of such a fluorine-substituted monomer or a copolymer of a fluorine-substituted monomer, or a mixture of a fluorine-substituted monomer and a non-fluorine-substituted monomer. Along with the fluorine atoms, the fluoropolymer may also be substituted with other halogen atoms, such as chlorine and bromine atoms. Representative monomers suitable for forming the fluoropolymers used in the present invention are tetrafluoroethylene, vinylidene fluoride, hexafluoropropylene, chlorotrifluoroethylene, perfluoroethyl vinyl ether, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, etc., and mixtures thereof. Specific examples of suitable fluoropolymers include polytetrafluoroethylene, perfluoroalkyl vinyl ethers, poly(tetrafluoroethylene-co-perfluoroalkyl vinyl ethers), fluorinated ethylene propylene copolymers, ethylene tetrafluoroethylene copolymers, polyvinylidene fluoride, polychlorotrifluoroethylene, and the like, and mixtures thereof.

[0050] II. formation

[0066] The components used to form the polymer composition may be combined together using any of a variety of different techniques known in the art. For example, in one particular embodiment, the liquid crystal polymer and other optional additives are melt processed as a mixture in an extruder to form the polymer composition. The mixture may be melt kneaded at a temperature of about 200°C to about 450°C in a single or multiple screw extruder. In one embodiment, the mixture may be melt processed in an extruder that includes multiple temperature zones. The temperature of the individual zones is typically set within about -60°C to about 25°C of the melting temperature of the polymer. By way of example, the mixture may be melt processed using a twin screw extruder such as a Leistritz 18mm co-rotating fully intermeshing twin screw extruder. A general purpose screw design may be used to melt process the mixture. In one embodiment, the mixture containing all of the components may be fed into the feed port of the first barrel by a metered feeder. In another embodiment, different components may be added at different addition points of the extruder as is known. For example, the polymer may be applied to the feed port, and certain additives (e.g., hydrophobic materials) may be fed at the same or different temperature zones located downstream therefrom. In either case, the resulting mixture can be melted, mixed, and then extruded through a die. The extruded polymer composition can then be quenched in a water bath to solidify, pelletized in a pelletizer, and then dried.

[0051]

[0067] In addition to being mixed during melt processing, additives can also be incorporated into the polymer matrix during the formation of the liquid crystal polymer. For example, the aromatic precursor monomers used to form the liquid crystal polymer can be reacted (e.g., in a polymerization apparatus) in the presence of additives such as hydrophobic materials. In this manner, the additives can be physically incorporated into the resulting polymer matrix. The additives can be introduced at any time, but are typically applied before melt polymerization is initiated, and typically with other aromatic precursor monomers for the polymer. The relative amount of additives fed into the reaction varies, but is typically about 0.1 wt.% to about 35 wt.%, in some embodiments about 0.5 wt.% to about 30 wt.%, and in some embodiments about 1 wt.% to about 25 wt.% of the reaction mixture.

[0052]

[0068] Regardless of the method by which the composition is formed, the resulting melt viscosity is generally sufficiently low so that it can be readily formed into a melt extruded substrate. For example, in one particular embodiment, the polymer composition is melt extruded at a viscosity of 1,000 s. -1 In some embodiments, the melt viscosity is about 500 Pa·s or less, and in some embodiments about 250 Pa·s or less, and in some embodiments, about 5 Pa·s to about 150 Pa·s, and in some embodiments, about 5 Pa·s to about 100 Pa·s, and in some embodiments, about 10 Pa·s to about 100 Pa·s, and in some embodiments, about 15 to about 90 Pa·s, determined at a shear rate of 100 Pa·s.

[0053] II. Electronic Components

[0069] As mentioned above, the polymer compositions may be utilized in a wide variety of electrical components of 5G systems, such as antenna structures, radio frequency ("RF") filters, circuit boards, etc. As used herein, "5G" generally refers to high-speed data communication by radio frequency signals. 5G networks and systems can communicate data at much higher speeds than previous generations of data communication standards (e.g., "4G", "LTE"). Various standards and specifications have been published that quantify the requirements for 5G communication. As an example, the International Telecommunications Union (ITU) published the International Mobile Telecommunications-2020 ("IMT-2020") standard in 2015. The IMT-2020 standard defines various data transmission criteria (e.g., downlink and uplink data rates, latency, etc.) for 5G. The IMT-2020 standard defines uplink and downlink peak data rates as the minimum data rates for uploading and downloading data that a 5G system must support. The IMT-2020 standard sets the downlink peak data rate requirement at 20 Gbit / s and the uplink peak data rate at 10 Gbit / s. rdThe Third Generation Partnership Project (3GPP®) recently published a new standard for 5G, called "5G NR." 3GPP® published "Release 15" in 2018, which defines "Phase 1" as the standardization of 5G NR. 3GPP® defines the 5G frequency band as "Frequency Range 1" (FR1), which generally includes frequencies below 6 GHz, and "Frequency Range 2" (FR2), which is a frequency band in the range of 20-60 GHz. However, as used herein, "5G frequency" may refer to systems that utilize frequencies greater than 60 GHz, e.g., in the ranges up to 80 GHz, up to 150 GHz, and up to 300 GHz. As used herein, "5G frequency" may refer to a frequency of about 2.5 GHz or higher, and in some embodiments, about 3.0 GHz or higher, and in some embodiments, about 3 GHz to about 300 GHz or higher, and in some embodiments, about 4 GHz to about 80 GHz, and in some embodiments, about 5 GHz to about 80 GHz, and in some embodiments, about 20 GHz to about 80 GHz, and in some embodiments, about 28 GHz to about 60 GHz.

[0054]

[0070] 5G antenna systems generally utilize high frequency antennas and antenna arrays used in base stations, repeaters (e.g., "femtocells"), relay stations, terminals, user devices, and / or other suitable components of a 5G system. Antenna elements / arrays and systems may meet or be considered "5G" based on standards published by 3GPP, such as Release 15 (2018), and / or IMT-2020 standards. To achieve such high speed data communications at high frequencies, antenna elements and arrays generally utilize small feature sizes / spacings (e.g., fine pitch technology) that can improve antenna performance. For example, feature sizes (spacing between antenna elements, width of antenna elements), etc., generally depend on the wavelength ("λ") of the desired transmit and / or receive radio frequency propagating through the substrate on which the antenna elements are formed (e.g., nλ / 4, where n is an integer). Additionally, beamforming and / or beamsteering can be utilized to facilitate transmission and reception across multiple frequency ranges or channels (e.g., multiple input multiple output (MIMO), massive MIMO). High frequency 5G antenna elements may have various configurations. For example, 5G antenna elements may be or include coplanar waveguide elements, patch arrays (e.g., mesh grid patch arrays), other suitable 5G antenna configurations. Antenna elements may be configured to provide MIMO, massive MIMO capabilities, beam steering, and the like. As used herein, "massive" MIMO capabilities generally refer to providing a large number of transmit and receive channels by an antenna array, for example, eight transmit (Tx) channels and eight receive (Rx) channels (abbreviated as 8x8). Massive MIMO capabilities may include 8x8, 12x12, 16x16, 32x32, 64x64, or more.

[0055]

[0071] Antenna elements may be fabricated using a variety of manufacturing techniques. Typically, such elements are formed on a substrate formable from the polymer composition of the present invention. As an example, antenna elements and / or associated elements (e.g., ground elements, feedlines, etc.) may utilize fine pitch technology. Fine pitch technology generally refers to small or fine spacing between their components or leads. For example, feature dimensions and / or spacing between antenna elements (or between antenna elements and ground planes) may be about 1,500 micrometers or less, in some embodiments 1,250 micrometers or less, in some embodiments 750 micrometers or less (e.g., center-to-center spacing of 1.5 mm or less), 650 micrometers or less, in some embodiments 550 micrometers or less, in some embodiments 450 micrometers or less, in some embodiments 350 micrometers or less, in some embodiments 250 micrometers or less, in some embodiments 150 micrometers or less, in some embodiments 100 micrometers or less, and in some embodiments 50 micrometers or less. However, it should be understood that smaller and / or larger feature sizes and / or spacings may also be utilized. As a result of such small feature sizes, antenna configurations and / or arrays having a large number of antenna elements within a small footprint can be achieved. For example, the antenna array may have an average antenna element density of more than 1,000 antenna elements per square centimeter, in some embodiments more than 2,000 antenna elements per square centimeter, in some embodiments more than 3,000 antenna elements per square centimeter, in some embodiments more than 4,000 antenna elements per square centimeter, in some embodiments more than 6,000 antenna elements per square centimeter, and in some embodiments more than about 8,000 antenna elements per square centimeter. Such a dense arrangement of antenna elements can provide a larger number of channels for MIMO functionality per unit area of ​​antenna area. For example, the number of channels may correspond to (e.g., be equal to or proportional to) the number of antenna elements.

[0056]

[0072] With reference to FIG. 1, for example, a 5G antenna system 100 may include a base station 102, one or more relay stations 104, one or more user computing devices 106, one or more Wi-Fi repeaters 108 (e.g., “femtocells”), and / or other suitable antenna components of a 5G antenna system 100. The relay stations 104 may be configured to relay or “repeat” signals between the base station 102 and the user computing devices 106 and / or the relay stations 104 to facilitate communication with the base station 102 by the user computing devices 106 and / or other relay stations 104. The base station 102 may include a MIMO antenna array 110 configured to receive and / or transmit radio frequency signals 112 with the relay stations 104, the Wi-Fi repeaters 108, and / or directly with the user computing devices 106. The user computing devices 106 is not necessarily limited by the present invention and includes devices such as 5G smartphones.

[0057]

[0073] The MIMO antenna array 110 may utilize beam steering to focus or direct radio frequency signals 112 to the relay station 104. For example, the MIMO antenna array 110 may be configured to adjust an elevation angle 114 with respect to a heading angle 116 defined in the XY and / or ZY planes, as well as with respect to the Z direction. Similarly, one or more of the relay station 104, user computing device 106, and Wi-Fi repeater 108 may utilize beam steering to improve reception and / or transmission capabilities to the MIMO antenna array 110 by directionally tuning the sensitivity and / or power transmission of the devices 104, 106, 108 with respect to the MIMO antenna array 110 of the base station 102 (e.g., by adjusting one or both of the relative elevation angle and / or relative azimuth angle of the respective devices).

[0058]

[0074] Similarly, Figures 2A-2B are top and side views, respectively, of an exemplary user computing device 106. The user computing device 106 may include one or more antenna elements 200, 202 (e.g., arranged as an antenna array). With reference to Figure 2A, the antenna elements 200, 202 may be configured to perform beam steering in the XY plane (indicated by arrows 204, 206, corresponding to relative azimuth angles). With reference to Figure 2B, the antenna elements 200, 202 may be configured to perform beam steering in the ZY plane (indicated by arrows 204, 206).

[0059]

[0075] FIG. 3 is a simplified schematic diagram of multiple antenna arrays 302 connected (e.g., with a front-end module) using respective feed lines 304. The antenna arrays 302 may be attached to a side 306 of a substrate 308 as described and illustrated with respect to FIGS. 4A-4C. The substrate 308 may contain the polymer composition of the present invention. The antenna array 302 may include multiple vertically connected elements (e.g., a mesh grid array). Thus, the antenna array 302 may extend generally parallel to the side 306 of the substrate 308. A shield may optionally be provided on the side 306 of the substrate 308 such that the antenna array 302 is located outside the shield with respect to the substrate 308. The vertical spacing distance between the vertically connected elements of the antenna array 302 may be determined by the antenna array 308 side 306. 302 Accordingly, in some embodiments, these spacing distances may be relatively small (e.g., less than about 750 micrometers) such that the antenna array 302 is a “fine pitch” antenna array 302.

[0060]

[0076] 4 is a side view of a configuration of a coplanar waveguide antenna 400. One or more coplanar ground layers 402 may be disposed parallel to an antenna element 404 (e.g., a patch antenna element). Another ground layer 406 may be spaced from the antenna element 404 by a substrate 408, which may be a circuit board such as those described herein. One or more additional antenna elements 410 may be spaced from the antenna element 404 by a second layer or substrate 412, which may contain a polymer composition of the present invention. The dimensions "G" and "W" may correspond to the "feature size" of the antenna 400. The "G" dimension may correspond to the distance between the antenna element 404 and the coplanar ground layer 406. The "W" dimension may correspond to the width (e.g., line width) of the antenna element 404. Thus, in some embodiments, the dimensions "G" and "W" may be relatively small (e.g., less than about 750 micrometers) such that the antenna 400 is a "fine pitch" antenna 400.

[0061]

[0077] FIG. 5A is a diagram of one embodiment of an antenna array 500. The antenna array 500 may include a substrate 510 and a plurality of antenna elements 520 formed thereon. The substrate 510 may contain a polymer composition of the present invention. The plurality of antenna elements 520 may be approximately uniformly sized in the X and / or Y directions (e.g., square or rectangular). The plurality of antenna elements 520 may be approximately uniformly spaced apart in the X and Y directions. The dimensions of and / or spacing between the antenna elements 520 may correspond to the "feature size" of the antenna array 500. Thus, in some embodiments, the dimensions and / or spacing may be relatively small (e.g., less than about 750 micrometers) such that the antenna array 500 is a "fine pitch" antenna array 500. As illustrated by ellipsis 522, the number of columns of antenna elements 520 illustrated in FIG. 5 is shown by way of example only. Similarly, the number of rows of antenna elements 520 is shown by way of example only.

[0062]

[0078] The tuned antenna array 500 can be used to provide massive MIMO capabilities, for example, in a base station (e.g., as described above with respect to FIG. 1). More specifically, radio frequency interactions between various elements may be controlled or tuned to provide multiple transmit and / or receive channels. The transmit power and / or receive sensitivity may be directionally controlled to focus or direct the radio frequency signal, for example, as described with respect to the radio frequency signal 112 of FIG. 1. The tuned antenna array 500 can provide a large number of antenna elements 522 within a small footprint. For example, the tuned antenna 500 may have an average antenna element density of 1,000 or more antenna elements per square centimeter. Such a dense arrangement of antenna elements can provide a larger number of channels for MIMO capabilities per unit area. For example, the number of channels may correspond to (e.g., be equal to or proportional to) the number of antenna elements.

[0063]

[0079] FIG. 5B is a diagram of an embodiment of an antenna array 540. The antenna array 540 may include a plurality of antenna elements 542 and a plurality of feed lines 544 connecting the antenna elements 542 (e.g., with other antenna elements 542, a front-end module, or other suitable components). The antenna elements 542 may have respective widths "w" and spacing distances "S1" and "S2" therebetween (e.g., in the X- and Y-directions, respectively). These dimensions may be selected to achieve 5G frequency communication at a desired 5G frequency. More specifically, the dimensions may be selected to tune the antenna array 540 to transmit and / or receive data using radio frequency signals within the 5G frequency spectrum (e.g., greater than 2.5 GHz and / or greater than 3 GHz and / or greater than 28 GHz). The dimensions may be selected based on material properties of a substrate that may contain the polymer composition of the present invention. For example, one or more of "w," "S1," or "S2" may correspond to a multiple of the propagation wavelengths ("λ") of the desired frequency through the substrate material (e.g., nλ / 4, where n is an integer).

[0064]

[0080] As an example, λ can be:

[0065]

number

[0066] (where c is the speed of light in a vacuum and ε R is the relative dielectric constant of the substrate (or surrounding material) and f is the desired frequency) It may be calculated as follows:

[0067]

[0081] 5C is a diagram of an exemplary antenna configuration 560 according to an embodiment of the invention. The antenna configuration 560 may include multiple antenna elements 562 disposed on parallel long sides of a substrate 564. The various antenna elements 562 may have respective lengths "L" (and spacing distances therebetween) that tune the antenna configuration 560 to receive and / or transmit at a desired frequency and / or frequency range. More particularly, such dimensions may be selected based on a propagation wavelength λ at a desired frequency for the substrate material, e.g., as described above with reference to FIG. 5B.

[0068]

[0082] Besides being used to form antenna elements (e.g., substrates), the polymer compositions may also be utilized in other electrical components of 5G systems. For example, RF filters include one or more resonant elements (e.g., piezoelectric materials, dielectric materials, etc.) that can produce resonant behavior in a narrow frequency band at the typically desired 5G frequencies. The specific configuration and operation of the filters may vary as known to those skilled in the art. For example, the RF filter may be an acoustic filter, such as a surface acoustic wave (SAW) filter, a bulk acoustic wave (BAW) filter, a film bulk acoustic resonator (FBAR or TFBAR), etc. Such acoustic filters generally utilize piezoelectric materials, such as quartz, lithium tantalate, lithium niobate, lanthanum gallium silicate, aluminum nitride, etc. For example, in SAW filters, an electrical input signal is converted into an acoustic wave by interleaved metallic interdigital transducers (IDTs) fabricated on a piezoelectric substrate. In BAW filters, a piezoelectric substrate is sandwiched between two electrodes and acoustically isolated from the surrounding medium. In this method, acoustic waves are excited and reflected by an electrical input signal, propagating vertically to form a standing acoustic wave. The thin outer layer acts as an acoustic reflector and prevents the acoustic wave from escaping into the substrate. In FBAR filters, a cavity is etched below the active region, so that the air / crystal interfaces on either side of the resonator trap the acoustic wave.

[0069]

[0083] Apart from acoustic filters, other types of RF filters can be used. For example, cavity filters may be utilized in which resonant elements (e.g., dielectric materials) are disposed within a number of cavities formed within a housing structure. One of the most frequently used resonators in cavity filters is a coaxial resonator structured to have a cylinder in which holes or recesses are formed. Suitable dielectric materials may include, for example, titanate-, niobate-, and / or tantalate (BZT)-based dielectric materials, such as barium titanate, strontium titanate, barium strontium titanate, and the like.

[0070]

[0084] Regardless of its particular configuration, an RF filter may utilize the polymer composition of the present invention, which has a low dielectric constant and dissipation factor, resulting in good performance in a wide variety of ways at 5G frequencies. For example, in an acoustic filter, the polymer composition may be used to form a substrate for supporting a resonating element (e.g., a piezoelectric material). In such an embodiment, the resonating element may be supported by the substrate by disposing the resonating element directly on the substrate. Alternatively, various other layers (e.g., reflective material, adhesive, etc.) may be located between the substrate and the resonating element. For example, referring to FIG. 6, an embodiment of a SAW filter 100 is shown in which an electrical input signal is provided via electrical ports 102 (i.e., I / O pads) and a piezoelectric substrate 104 is provided. 606 10. If desired, a piezoelectric substrate 104 may be formed from the polymer composition of the present invention. 606 7, an embodiment of a BAW filter 100 is shown in which a piezoelectric substrate 108 is provided. 616 1 is disposed between an upper metal layer 112 and a lower metal layer (not shown). In this manner, acoustic waves are excited in response to an electrical input signal provided thereto via an electrical port 118. If desired, a piezoelectric substrate formed from the polymer composition of the present invention may be used. 616A substrate 128 supporting the may also be provided, either directly or indirectly through a metal layer. When the polymer composition is applied to a substrate such as that shown in FIG. 6 or FIG. 7, it may optionally include a laser activatable additive so that laser direct structuring ("LDS") can be used to subsequently form conductive elements (e.g., transducers, metal layers, etc.) on the substrate. Activation with a laser results in a physicochemical reaction that cracks the spinel crystals and liberates metal atoms. These metal atoms may act as nuclei for metallization (e.g., reductive copper coating). Additionally, the laser creates a microscopically irregular surface and abrades the polymer matrix to create numerous microscopic depressions and grooves in which metal can adhere during metallization.

[0071]

[0085] As mentioned above, the RF filter may also include a housing that covers one or more elements of the filter (e.g., resonant element, supporting substrate, etc.) to form an individual package. In such an embodiment, the housing may be made from a polymer composition of the present invention. For example, referring to FIG. 8, an example of an RF filter package 10 is shown, which contains a resonant element 14 (e.g., a piezoelectric material) supported by a substrate 18 as described above. In this embodiment, an adhesive 24 is used to adhere the substrate 18 to the resonant element 14, although this is by no means required. If desired, the substrate 18 may be formed from a polymer composition of the present invention. A housing 20 may also be provided that covers the resonant element 14 and the substrate 18 to provide protection and structural integrity. If desired, the housing 20 may be formed from a polymer composition of the present invention. Optionally, a via 26 is formed through the substrate 18 that extends to the resonant element 14. Metal traces 28 are then formed / patterned in the package 10 to provide electrical connections therein, the traces 28 being formed in the vias 26 to I / O pads 30 on the front side of the resonant element 14, and out to the surface of the dielectric layer 18. The polymer composition used for the substrate 18 and / or housing 20 may optionally include a laser activatable additive so that a laser direct structuring process ("LDS") may be used to form the interconnects 28 and / or pads 30. If desired, air cavities 34 may also be provided in the adhesive layer 24 to allow proper vibration and associated generation of acoustic waves by the resonant element 14. Input / output (I / O) connections 38 (e.g., solder balls) may also be provided on the metal traces 28 to connect the package 10 to an external device (not shown), such as a printed circuit board.

[0072]

[0086] In the embodiments discussed above and illustrated in Figures 6-8, the polymer compositions of the present invention are utilized in an acoustic RF filter. However, as noted above, a variety of other RF filter configurations may also utilize the polymer compositions. For example, in one embodiment, the RF filter may be a cavity filter. For example, referring to Figure 9, one embodiment of a cavity filter 1000 is shown, which includes a housing. 1100and a cover 1110, one or both of which may be formed from the polymer composition of the present invention. As shown, a plurality of cavities 1102 may be formed within the housing 1100 in which the resonant element 1104 may be located. A suitable resonant element 1104 for this purpose may include, for example, a dielectric material. Although not required, the resonant element 1104 may have a cylindrical shape, with a recess or hole formed in at least a portion of the cylinder. Of course, a disk-shaped resonator may also be used if desired, and resonators having any of a variety of known shapes are applicable to embodiments of the present invention. The resonant element 1104 may be coupled to the bottom of the cavity by using bolts or the like. If desired, the housing 1100 may contain a metal plating (e.g., silver or copper), which may be formed by laser direct structuring if the polymer composition contains a laser metal activatable additive. The filter housing 1100 and cover 1110 may have a ground potential, and a pressing member 2000 may be used in the insertion area 1450 to provide the pressure required for tight pressing to facilitate obtaining desired electrical properties and providing good fastening. The location of the insertion area 1450 formed in the cover 1110 may correspond to the location of the resonator 1104.

[0073]

[0087] In addition to RF filters, the polymer composition may also be utilized in other components of a 5G system. For example, in one embodiment, the polymer composition may be utilized in a circuit board (e.g., a printed circuit board) of a 5G system. The antenna element may be applied (e.g., printed) directly to the circuit board, or alternatively, may be provided in an antenna module supported by and connected to the circuit board. For example, referring to FIG. 13, an embodiment of an electronic device 140 is shown, which contains a substrate 154 supporting various electrical components 142, such as integrated circuits (e.g., transceiver circuitry, control circuitry, etc.), individual components (e.g., capacitors, inductors, resistors), switches, etc. An encapsulant material 156 may be applied to the printed circuit board 154, which contains the components 142, as well as conductive traces 152 and contact pads 150 for forming electrical signal paths, such as those described herein. Semiconductor dies 144 may also be utilized, which are bonded to the printed circuit board and embedded in an enclosure to form each individual component 142. More specifically, the component 142 may have contacts 146 (e.g., solder pads) and may be attached to contacts 150 on a printed circuit board 154 using a conductive material 148 (e.g., solder) coupled between the contacts 146 and the contacts 150. In the illustrated embodiment, the antenna element 160 is formed on an exposed surface of the encapsulation material 156. The antenna element 156 may be electrically connected to the printed circuit board 154 via a transmission line 158 (e.g., a metal post).

[0074]

[0088] The circuit board may have a laminate structure that contains a film disposed adjacent to the conductive layer. In such an embodiment, the film may be formed from the polymer composition of the present invention. Any of a variety of different techniques may generally be used to form the polymer composition into a film. Suitable techniques may include, for example, solvent casting, melt extrusion (e.g., die casting, blown film casting, extrusion coating, etc.). In one particular embodiment, a blown film process is utilized in which the composition is fed into an extruder and melt processed before being fed through a blown film die to form a molten bubble. Typically, the die contains a mandrel located inside the outer die body, thus defining a space between them. The polymer composition is blown through this space to form a bubble, which is then drawn out and expanded with air, and cooled rapidly so that the polymer composition is rapidly solidified. If desired, the bubble may then be broken between rollers and optionally wound onto a reel. The thickness of the resulting film may vary, but is typically about 500 micrometers or less, in some embodiments from about 1 to about 250 micrometers, in some embodiments, from about 2 to about 100 micrometers, in some embodiments, from about 3 to about 50 micrometers, and in some embodiments, from about 5 to about 30 micrometers.

[0075]

[0089] As described above, the film is located adjacent to at least one conductive layer to form a laminate. The conductive layer may be provided in a variety of different forms, such as a membrane, film, mold, wafer, tube, etc. For example, the layer may have a foil-like structure in that it has a relatively thin thickness, for example, about 500 micrometers or less, in some embodiments about 200 micrometers or less, and in some embodiments, about 1 to about 100 micrometers. Of course, larger thicknesses are also available. The conductive layer may also contain various conductive materials, such as metals, for example, gold, silver, nickel, aluminum, copper, and mixtures or alloys thereof. For example, in one embodiment, the conductive layer may include copper (e.g., pure copper and copper alloys). The film may be applied to the conductive layer using techniques such as those described above (e.g., casting), or the conductive layer may alternatively be applied to the film using techniques such as ion beam sputtering, radio frequency sputtering, direct current magnetron sputtering, glow discharge, etc. If desired, the film may be surface treated on the side facing the conductive layer to improve adhesion between the film and the conductive layer. Examples of such surface treatments include, for example, corona discharge treatment, UV irradiation treatment, plasma treatment, and the like. When applied to a conductive layer, the film may be optionally annealed to improve its properties. For example, annealing may be performed at a temperature of about 250°C to about 400°C, in some embodiments about 260°C to about 350°C, in some embodiments about 280°C to about 330°C, for a period ranging from about 15 minutes to about 300 minutes, in some embodiments about 20 minutes to about 200 minutes, in some embodiments about 30 minutes to about 120 minutes. During annealing, it may be desirable to restrain the film at one or more points (e.g., edges) so that the film cannot physically move generally. This can be accomplished in a variety of ways, such as by clamping, taping, or otherwise adhering the film to the conductive layer.

[0076]

[0090] The laminate may have a two-layer structure containing only a film and a conductive layer. For example, referring to FIG. 10, an embodiment of a two-layer structure 10 is shown containing a film 11 located adjacent to a conductive layer 12 (e.g., copper foil). Alternatively, a multi-layer laminate may be formed containing two or more conductive layers and / or two or more films. For example, referring to FIG. 11, an embodiment of a three-layer laminate structure 100 is shown containing a film 110 located between two conductive layers 112. Yet another embodiment is shown in FIG. 12. In this embodiment, a seven-layer laminate structure 200 is shown containing a core 201 formed from a film 210 located between two conductive layers 212. A film 220 similarly covers each of the conductive layers 212, respectively, and an outer conductive layer 222 covers the film 220. In the above-mentioned embodiment, a film may be used to form any or even all of the film layers. Various conventional processing steps may be utilized to provide a laminate with sufficient strength. For example, the laminate may be subjected to pressing and / or heat treatment as known in the art.

[0077]

[0091] The invention may be better understood with reference to the following examples. EXAMPLES

[0078] Test Method

[0092] Melt viscosity: Melt viscosity (Pa s) was measured at a shear rate of 1,000 s using a Dynisco LCR7001 capillary rheometer. -1 and 15°C above the melt temperature (e.g., about 350°C) according to ISO Test No. 11443:2005. The rheometer orifice (die) had a diameter of 1 mm, a length of 20 mm, an L / D ratio of 20.1, and an entrance angle of 180°. The barrel diameter was 9.55 mm + 0.005 mm and the rod length was 233.4 mm.

[0079]

[0093] Melting temperature: Melting temperature ("Tm") may be determined by differential scanning calorimetry ("DSC") as known in the art. Melting temperature is the differential scanning calorimetry (DSC) peak melting temperature as determined by ISO test No. 11357-2:2013. Based on the DSC procedure, samples were heated and cooled at 20°C per minute using DSC measurements performed on a TA Q2000 instrument as described in ISO standard 10350.

[0080]

[0094] Deflection Temperature Under Load ("DTUL"): Deflection temperature under load may be determined according to ISO Test No. 75-2:2013 (technically equivalent to ASTM D648-07). More specifically, a test specimen sample of 80 mm length, 10 mm thickness, and 4 mm width may be subjected to an edgewise three-point bend test with a specified load (maximum external fiber stress) of 1.8 megapascals. The specimen is lowered into a silicone oil bath and the temperature is increased at 2°C per minute until the specimen deflects 0.25 mm (0.32 mm per ISO Test No. 75-2:2013).

[0081]

[0095] Tensile modulus, tensile stress and tensile elongation: Tensile properties may be tested according to ISO Test No. 527:2012 (technically equivalent to ASTM D638-14). Modulus and strength measurements may be performed on the same test specimen sample of 80 mm length, 10 mm thickness, and 4 mm width. The test temperature may be about 23°C, and the test speed may be 1 or 5 mm / min.

[0082]

[0096] Flexural modulus, flexural stress and flexural elongation: Flexural properties may be tested according to ISO Test No. 178:2010 (technically equivalent to ASTM D790-10). The test may be performed on a support span of 64 mm. The test may be performed on the center of an uncut ISO 3167 multipurpose bar. The test temperature may be about 23°C and the test speed may be 2 mm / min.

[0083]

[0097] Unnotched and Notched Charpy Impact Strength: Charpy properties may be tested according to ISO Test No. ISO179-1:2010 (technically equivalent to ASTM D256-10, Method B). This test may be performed using a Type 1 specimen size (80 mm length, 10 mm width, and 4 mm thickness). When testing notched impact strength, the notch may be a Type A notch (0.25 mm base radius). Specimens may be cut from the center of the multipurpose bar using a single-tooth milling machine. The test temperature may be about 23°C.

[0084]

[0098] Dielectric constant ("Dk") and dissipation factor ("Df"): The dielectric constant (or relative static permittivity) and dissipation factor are determined in accordance with IEC 60250:1969. Such techniques are also described in Baker-Jarvis, et al., IEEE Trans. on Dielectric and Electrical Insulation, 5(4), 571 (1998) and Krupka, et al., Proc. th This is described in International Conference on Dielectric Materials: Measurements and Applications, IEEE Conference Publication No. 430 (September 1996). More specifically, a plate-shaped sample of size 80 mm x 80 mm x 1 mm was inserted between two fixed dielectric resonators. The resonators measured the dielectric constant components in the plane of the specimen. Five samples may be tested and the average value is recorded.

[0085] Example 1

[0099] Samples 1-2 are formed for use in 5G systems. LCP1 is formed from 60% HBA, 4% HNA, 18% TA, and 18% BP. LCP2 is formed from 48% HNA, 2% HBA, 25% BP, and 25% TA. Compounding was performed using an 18 mm single screw extruder. Samples are injection molded into plaques (60 mm x 60 mm). The compounding is described below.

[0086] [Table 1]

[0087]

[0100] Samples 1-2 were tested for thermal and mechanical properties and the results are listed below.

[0088] [Table 2]

[0089] Example 2

[0101] Samples 3-5 were extruded into films for use in 5G systems. Sample 3 contained 100 wt.% LCP3 formed from 73% HBA and 27% HNA. Sample 4 contained 100 wt.% LCP4 formed from 79.3% HBA, 20% HNA and 0.7% TA. Sample 5 contained 75 wt.% LCP3 and 25 wt.% PTFE. Samples 3-5 were tested for thermal and mechanical properties. The results are described below.

[0090] [Table 3]

[0091] Example 3

[0102] Samples 6-8 were extruded into films for use in printed circuit boards. Sample 6 contained 80 wt.% LCP5 and 20 wt.% PTFE, Sample 7 contained 75 wt.% LCP5 and 25 wt.% PTFE1, and Sample 8 contained 75 wt.% LCP4 and 25 wt.% PTFE. LCP5 was formed from 43% HBA, 9% TA, 29% HQ, and 20% NDA. PTFE1 also had a D50 particle size of 4 μm and a D90 particle size of 15 μm. Samples 6-8 were tested for thermal and mechanical properties. The results are listed below.

[0092] [Table 4]

[0093] Example 4

[0103] Samples 9-15 are formed from various combinations of liquid crystal polymers (LCP1 and LCP5), copper chromite filler (CuCr2O4), glass fiber, alumina trihydrate ("ATH"), lubricant (polyethylene wax), and polytetrafluoroethylene ("PTFE1" or "PTFE2"). PTFE2 is a powder of polytetrafluoroethylene particles with a D50 particle size of 40 μm. Compounding was performed using an 18 mm single screw extruder. Parts are injection molded and samples are molded into plaques (60 mm x 60 mm).

[0094] [Table 5]

[0095]

[0104] Samples 9-15 were tested for thermal and mechanical properties and the results are listed in Table 2 below.

[0096] [Table 6]

[0097] Example 5

[0105] Sample 16 contains 100 wt.% LCP6 ​​for use in 5G systems, which is made of 62% HNA, 2% HBA, 18% TA and 18% BP. The sample is injection molded into a plaque (60mm x 60mm) and tested for thermal and mechanical properties. The results are listed below.

[0098] [Table 7]

[0099] Example 6

[0106] Samples 17-24 are formed from various combinations of liquid crystal polymer (LCP2), milled and / or flattened chopped glass fiber strands (aspect ratio=4), mica (MICA1 and MICA2) and silica. MICA1 had an average particle size of 25 micrometers and MICA2 had an average particle size of 60 micrometers. Compounding was performed using an 18 mm single screw extruder. Parts were injection molded and samples were molded into plaques (60 mm x 60 mm).

[0100] [Table 8]

[0101]

[0107] Samples 17-24 were tested for thermal and mechanical properties and the results are listed in the table below.

[0102] [Table 9]

[0103] Example 7

[0108] Samples 25-30 are formed from liquid crystal polymer (LCP5 or LCP2), hollow glass spheres, and mica, wollastonite, glass powder, and / or glass fibers. The hollow glass spheres had an average diameter of 18 micrometers. The glass powder had a relative dielectric constant of 4.8 determined at a frequency of 1 GHz. Additionally, the glass fibers utilized had an initial length of either 3 mm or 4 mm. The polymer compositions may also include polyethylene lubricant, alumina trihydrate, pigments, and / or various other minor additives. Compounding was performed using a 25 mm single screw extruder.

[0104] [Table 10]

[0105]

[0109] The samples were then tested for thermal and mechanical properties, and the results are set forth in Table 4 below.

[0106] [Table 11]

[0107] Example 8

[0110] Sample 31 is formed from liquid crystal polymers (LCP2 and LCP7), hollow glass spheres, glass powder, glass fiber, and alumina trihydrate. LCP7 is formed from 60% HBA, 4% HNA, 18% TA, and 18% BP. The glass powder had a relative dielectric constant of 4.8 determined at a frequency of 1 GHz. Compounding was performed using a 25 mm single screw extruder.

[0108] [Table 12]

[0109]

[0111] The samples were then tested for thermal and mechanical properties, and the results are set forth in Table 6 below.

[0110] [Table 13]

[0111] Example 9

[0112] Sample 33 contains 100 wt.% LCP8 for use in 5G systems, which is made of 73% HNA and 27% HBA. The sample is injection molded into a plaque (60 mm x 60 mm) and tested for thermal and mechanical properties. The results are listed below.

[0112] [Table 14]

[0113] Example 10

[0113] Sample 34 contains 100 wt.% LCP9 for use in 5G systems, which is made of 78% HNA, 2% HBA, 10% TA and 10% BP. The sample is injection molded into a plaque (60 mm x 60 mm) and tested for thermal and mechanical properties. The results are listed below.

[0114] [Table 15]

[0115] Example 11

[0114] Sample 35 contains 100 wt.% LCP10 for use in 5G systems, which is made of 79% HNA, 2% HBA, 14% TA and 14% BP. The sample is injection molded into a plaque (60 mm x 60 mm) and tested for thermal and mechanical properties. The results are listed below.

[0116] [Table 16]

[0117] Example 12

[0115] Sample 36 contains 100 wt.% LCP11 for use in 5G systems, which is made of 48% HNA, 2% HBA, 25% NDA and 25% BP. The sample is injection molded into a plaque (60 mm x 60 mm) and tested for thermal and mechanical properties. The results are listed below.

[0118] [Table 17]

[0119] Example 13

[0116] Sample 37 contains 100 wt.% LCP12 for use in 5G systems, which is made of 76% HNA and 24% HBA. The sample is injection molded into a plaque (60 mm x 60 mm) and tested for thermal and mechanical properties. The results are listed below.

[0120] [Table 18]

[0121] Example 14

[0117] Samples 38-39 are made from various combinations of liquid crystal polymers (LCP12 and LCP6) and PTFE1. Compounding was carried out using an 18 mm single screw extruder. Parts were injection molded and samples were molded into plaques (60 mm x 60 mm).

[0122] [Table 19]

[0123]

[0118] Samples 38-39 were tested for thermal and mechanical properties, and the results are set forth in Table 7 below.

[0124] [Table 20]

[0125] Example 15

[0119] Samples 40-41 were extruded into films for use in printed circuit boards. Sample 40 contained 70 wt.% LCP5 and 30 wt.% PTFE1, and Sample 41 contained 65 wt.% LCP5 and 35 wt.% PTFE1. Samples 40-41 were tested for thermal and mechanical properties. The results are listed below.

[0126] [Table 21]

[0127]

[0120] These and other modifications and variations of the present invention are intended to be within the spirit and scope of the present invention. It will be understood that the present invention can be practiced by those skilled in the art without departing from the spirit and scope of the present invention. Moreover, it should be understood that aspects of the various embodiments may be interchanged both in whole or in part. Moreover, those skilled in the art will appreciate that the foregoing description is merely illustrative, and thus does not limit the invention as further described in the appended claims. The claims as filed are set forth below. [Claim 1] 1. A 5G system comprising at least one antenna element configured to transmit and receive 5G radio frequency signals, and at least one electronic component, wherein the antenna element, the electronic component, or both comprise a polymer composition comprising a liquid crystal polymer containing repeat units derived from naphthenic hydroxycarboxylic acids and / or naphthenic dicarboxylic acids in an amount of about 10 mol.% or more, and further wherein the polymer composition exhibits a dielectric constant of about 5 or less and a dielectric loss tangent of about 0.05 or less at a frequency of 10 GHz. [Claim 2] 2. The 5G system of claim 1, wherein the polymer composition has a melting temperature of about 200°C to about 400°C. [Claim 3] 3. The 5G system of claim 1 or 2, wherein the liquid crystal polymer constitutes about 40 wt.% to about 99 wt.% of the polymer composition. [Claim 4] 4. The 5G system of claim 1, wherein the liquid crystal polymer contains repeat units derived from one or more aromatic dicarboxylic acids, one or more aromatic hydroxycarboxylic acids, or a combination thereof. [Claim 5] 5. The 5G system of claim 4, wherein the aromatic hydroxycarboxylic acid comprises 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, or a combination thereof. [Claim 6] 5. The 5G system of claim 4, wherein the aromatic hydroxycarboxylic acid comprises terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, or a combination thereof. [Claim 7] 5. The 5G system of claim 4, wherein the liquid crystal polymer further contains repeat units derived from one or more aromatic diols. [Claim 8] 8. The 5G system of claim 7, wherein the aromatic diol comprises hydroquinone, 4,4'-biphenol, or a combination thereof. [Claim 9] 9. The 5G system of claim 1, wherein the liquid crystal polymer is fully aromatic. [Claim 10] 10. The 5G system of claim 1, wherein the liquid crystal polymer contains repeat units derived from 6-hydroxy-2-naphthoic acid in an amount of about 30 mol.% or more. [Claim 11] The 5G system of claim 10, wherein the liquid crystal polymer contains repeat units derived from 6-hydroxy-2-naphthoic acid in an amount of about 50 mol.% or more. [Claim 12] The 5G system of claim 10, wherein the liquid crystal polymer contains repeat units derived from 6-hydroxy-2-naphthoic acid in an amount of about 70 mol.% or more. [Claim 13] The 5G system of claim 10, wherein the liquid crystal polymer contains repeating units derived from 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid in a molar ratio of about 0.1 to about 40. [Claim 14] 11. The 5G system of claim 10, wherein the liquid crystal polymer contains repeating units derived from 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid in a molar ratio of about 1 to about 5. [Claim 15] 15. A 5G system according to any one of claims 1 to 14, wherein the liquid crystal polymer contains repeating units derived from 2,6-naphthalenedicarboxylic acid in an amount of about 10 mol.% or more. [Claim 16] 16. The 5G system of claim 1, wherein the liquid crystal polymer exhibits a water absorption rate of about 0.015% or less after immersion in water for 24 hours according to ISO 62-1:2008. [Claim 17] 17. The 5G system of claim 1, wherein the liquid crystal polymer exhibits a moisture absorption of about 0.01% or less after exposure to 50% relative humidity at a temperature of 23° C. according to ISO 62-4:2008. [Claim 18] 18. A 5G system as described in any one of claims 1 to 17, wherein the liquid crystal polymer constitutes 100 wt.% of the composition. [Claim 19] 19. The 5G system of claim 1, wherein the additive comprises between about 1 wt.% and about 60 wt.% of the polymer composition, and the liquid crystal polymer comprises between about 40 wt.% and about 99 wt.% of the polymer composition. [Claim 20] 20. The 5G system of claim 1, wherein the polymer composition further comprises a fibrous filler. [Claim 21] 21. The 5G system of claim 20, wherein the fibrous filler comprises glass fibers. [Claim 22] 21. The 5G system of claim 20, wherein the fibrous filler has an aspect ratio of about 2 or greater. [Claim 23] 23. The 5G system of any of claims 1 to 22, wherein the polymer composition further comprises a particulate filler. [Claim 24] 24. The 5G system of claim 23, wherein the particulate filler comprises mica. [Claim 25] 25. The 5G system of claim 1 , wherein the polymer composition further comprises a laser activatable additive. [Claim 26] 26. The 5G system of any one of claims 1 to 25, wherein the polymer composition further comprises a hollow inorganic filler. [Claim 27] 27. The 5G system of any one of claims 1 to 26, wherein the polymer composition exhibits a relative dielectric constant of about 1.5 to about 4 at a frequency of 2 GHz. [Claim 28] 28. The 5G system of any of claims 1 to 27, wherein the polymer composition exhibits a dielectric tangent of less than or equal to about 0.0009 at a frequency of 2 GHz. [Claim 29] 29. The 5G system of claim 1 , wherein the antenna element is disposed on a substrate, the substrate comprising the polymer composition. [Claim 30] 30. The 5G system of claim 1, wherein the electronic component is a circuit board containing a film disposed on a conductive layer, the film containing the polymer composition. [Claim 31] 31. A 5G system according to any of claims 1 to 30, wherein the electronic component is an acoustic filter comprising a substrate supporting a piezoelectric material and a housing covering the piezoelectric material, the substrate, the housing, or both comprising the polymer composition. [Claim 32] 32. The 5G system of any of claims 1 to 31, wherein the electronic component is a cavity filter including a housing defining a cavity in which a dielectric material is received, the housing containing the polymer composition. [Claim 33] 33. The 5G system of claim 1, wherein the antenna elements have a feature size of less than about 1,500 micrometers. [Claim 34] 34. A 5G system as claimed in any preceding claim, wherein the 5G radio frequency signal has a frequency greater than about 28 GHz. [Claim 35] 35. The 5G system of claim 1, wherein the at least one antenna element comprises a plurality of antenna elements arranged in an antenna array. [Claim 36] 36. The 5G system of claim 35, wherein the plurality of antenna elements are separated by a spacing distance of less than about 1,500 micrometers. [Claim 37] 36. The 5G system of claim 35, wherein the plurality of antenna elements includes at least 16 antenna elements. [Claim 38] 36. The 5G system of claim 35, wherein the plurality of antenna elements are arranged in a grid. [Claim 39] 36. The 5G system of claim 35, wherein the antenna array is configured for at least eight transmit channels and at least eight receive channels. [Claim 40] 36. The 5G system of claim 35, wherein the antenna array has an average antenna element density of greater than 1,000 antenna elements per square centimeter. [Claim 41] 41. A 5G system as claimed in any preceding claim, further comprising a base station, the base station comprising the antenna element. [Claim 42] 42. A 5G system according to any preceding claim, further comprising at least one of a user computing device or a repeater, wherein at least one of the user computing device or the repeater base station comprises the antenna element.

Claims

1. 1. A 5G system comprising at least one antenna element configured to transmit and receive 5G radio frequency signals, and at least one electronic component, wherein the antenna element, the electronic component, or both, comprise a polymer composition comprising a liquid crystal polymer containing repeat units derived from naphthenic hydroxycarboxylic acids and / or naphthenic dicarboxylic acids in an amount of about 10 mol. % or greater, and further wherein the polymer composition exhibits a dielectric constant of about 5 or less and a dissipation factor of about 0.05 or less at a frequency of 10 GHz.

2. 10. The 5G system of claim 1, wherein the polymer composition has a melting temperature of about 200°C to about 400°C.

3. 3. The 5G system of claim 1 or 2, wherein the liquid crystal polymer comprises about 40 wt.% to about 99 wt.% of the polymer composition.

4. 4. The 5G system of claim 1, wherein the liquid crystal polymer contains repeat units derived from one or more aromatic dicarboxylic acids, one or more aromatic hydroxycarboxylic acids, or a combination thereof.

5. 5. The 5G system of claim 4, wherein the aromatic hydroxycarboxylic acid comprises 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, or a combination thereof.

6. 5. The 5G system of claim 4, wherein the aromatic dicarboxylic acid comprises terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, or a combination thereof.

7. 5. The 5G system of claim 4, wherein the liquid crystal polymer further contains repeat units derived from one or more aromatic diols.

8. 8. The 5G system of claim 7, wherein the aromatic diol comprises hydroquinone, 4,4'-biphenol, or a combination thereof.

9. 9. The 5G system of claim 1 , wherein the liquid crystal polymer is fully aromatic.

10. The 5G system according to any one of claims 1 to 9, wherein the liquid crystal polymer contains a repeating unit derived from 6-hydroxy-2-naphthoic acid in an amount of about 30 mol.% or more.

11. The 5G system according to claim 10, wherein the liquid crystal polymer contains a repeating unit derived from 6-hydroxy-2-naphthoic acid in an amount of about 50 mol. % or more.

12. The 5G system according to claim 10, wherein the liquid crystal polymer contains repeating units derived from 6-hydroxy-2-naphthoic acid in an amount of about 70 mol. % or more.

13. The 5G system of claim 10, wherein the liquid crystal polymer contains repeat units derived from 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid in a molar ratio of about 0.1 to about 40.

14. 11. The 5G system of claim 10, wherein the liquid crystal polymer contains repeat units derived from 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid in a molar ratio of about 1 to about 5.

15. The 5G system according to any one of claims 1 to 14, wherein the liquid crystal polymer contains a repeating unit derived from 2,6-naphthalenedicarboxylic acid in an amount of about 10 mol. % or more.

16. The 5G system of any one of claims 1 to 15, wherein the liquid crystal polymer exhibits a water absorption rate of about 0.015% or less after immersion in water for 24 hours according to ISO 62-1:2008.

17. 17. The 5G system of any one of claims 1 to 16, wherein the liquid crystal polymer exhibits a moisture absorption of about 0.01% or less after exposure to 50% relative humidity at a temperature of 23°C according to ISO 62-4:2008.

18. 18. The 5G system of claim 1 , wherein the liquid crystal polymer comprises 100 wt. % of the composition.

19. 19. The 5G system of any of claims 1 to 18, wherein the additive comprises from about 1 wt. % to about 60 wt. % of the polymer composition, and the liquid crystal polymer comprises from about 40 wt. % to about 99 wt. % of the polymer composition.

20. 20. The 5G system of claim 1, wherein the polymer composition further comprises a fibrous filler.

21. 21. The 5G system of claim 20, wherein the fibrous filler comprises glass fiber.

22. 21. The 5G system of claim 20, wherein the fibrous filler has an aspect ratio of about 2 or greater.

23. 23. The 5G system of any of claims 1 to 22, wherein the polymer composition further comprises a particulate filler.

24. 24. The 5G system of claim 23, wherein the particulate filler comprises mica.

25. 25. The 5G system of any of claims 1 to 24, wherein the polymer composition further comprises a laser activatable additive.

26. 26. The 5G system of any one of claims 1 to 25, wherein the polymer composition further comprises a hollow inorganic filler.

27. 27. The 5G system of any of claims 1 to 26, wherein the polymer composition exhibits a dielectric constant of about 1.5 to about 4 at a frequency of 2 GHz.

28. 28. The 5G system of any of claims 1 to 27, wherein the polymer composition exhibits a dissipation factor of less than or equal to about 0.0009 at a frequency of 2 GHz.

29. 29. The 5G system of claim 1 , wherein the antenna element is disposed on a substrate, the substrate comprising the polymer composition.

30. 30. The 5G system of claim 1 , wherein the electronic component is a circuit board containing a film disposed on a conductive layer, the film containing the polymer composition.

31. 31. The 5G system of claim 1 , wherein the electronic component is an acoustic filter including a substrate supporting a piezoelectric material and a housing covering the piezoelectric material, the substrate, the housing, or both including the polymer composition.

32. 32. The 5G system of any of claims 1 to 31, wherein the electronic component is a cavity filter including a housing defining a cavity in which a dielectric material is received, the housing containing the polymer composition.

33. A 5G system as described in any of claims 1 to 32, wherein the spacing between the antenna elements or the width of the antenna elements is less than about 1,500 micrometers.

34. 34. The 5G system of claim 1 , wherein the at least one antenna element comprises a plurality of antenna elements arranged in an antenna array.

35. 35. The 5G system of claim 34, wherein the plurality of antenna elements are separated by a spacing distance of less than about 1,500 micrometers.

36. 35. The 5G system of claim 34, wherein the plurality of antenna elements includes at least 16 antenna elements.

37. 35. The 5G system of claim 34, wherein the plurality of antenna elements are arranged in a grid.

38. 35. The 5G system of claim 34, wherein the antenna array is configured for at least eight transmit channels and at least eight receive channels.

39. 35. The 5G system of claim 34, wherein the antenna array has an average antenna element density of greater than 1,000 antenna elements per square centimeter.

40. 40. The 5G system of claim 1, further comprising a base station, the base station comprising the antenna element.

41. 41. A 5G system as described in any preceding claim, further comprising at least one of a user computing device or a repeater, wherein at least one of the user computing device or the repeater comprises the antenna element.

Citation Information

Patent Citations

  • Thermoplastic composition for use in forming laser-direct structured substrates

    JP2015502418A

  • Multi-antenna module and portable terminal

    JP2019080298A

  • Thermoplastic liquid crystal polymer and film of same

    WO2018181222A1